Multivariate analysis highlights genetic structure in Olive (Olea Europaea L.) germplasm using Resource-Efficient RAPD marker system - Ayesha Wadood; Amjad Hameed; Muhammad Yussouf Saleem; Abdul Rehman Khan; Saba Akram (Molecular Biology Reports, 2026)

Draft nuclear and complete mitochondrial genome assemblies of the flare-horned markhor (Capra falconeri): genomic resources for conservation and phylogenetics - Javeria Wali; Muhammad Waqas; Azhar Hussain Shah; Inam Ullah; Asif Mir; Zunnan Huang; Amjad Ali (Mammalian Genome, 2026)

Nature-Inspired Nanocomposites for Toxic Heavy Metals Removal: An Overview - Mudassar SanaUllah; Awais Ali Aslam; Abhishek Thakur; Sania Amjad; Shahzaib Ishfaq; Sadaf Ul Hassan; Usman Haidar; Muhammad Shahid Nazir; Mahmood Ahmed; Marek Kowalczuk (Reviews of Environmental Contamination and Toxicology, 2026)

Sustainable postharvest disease management: Integrating biological insights, technological innovations, omics, and precision strategies - Amjad Ali; Shreya Singh; Noor Fatima; Muhammed Tatar; Muhammad Shahbaz (Postharvest Biology and Technology, 2026)

Precision nanoparticles for plant thermotolerance: From molecular mechanisms to scalable agriculture - Muhammad Azeem Ashraf; Muhammad Ateeq; Muhammad Amjad; Qingfeng Dong; Hao Ren; Asad Shehzaib; Wang Xue; Liang Chen; Yin-Gang Hu (Plant Science, 2026)

Pathogen-induced physiological reprogramming and systemic dysfunction in plants - Mubashir Sharif; Muhammad Annas Shahid; Mahad Ur-Rehman; Ikhlas Shafique; Muhammad Farooq; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2026)

Moderate maize canopy defoliation improves light distribution, crop yields, and soybean seed quality in additive maize-soybean intercropping - Muhammad Ali Raza; Wang Zhiqi; Amjad Saeed; Hina Gul; Hassan Shehryar Yasin; Asif Naveed Ranjha; Zaheer Ahmed; Ghulam Raza; Wopke Van Der Werf; Akash Fatima; Xue Liang; Muhammad Hayder Bin Khalid; et al. (Field Crops Research, 2026)

Multi-model drought index for Pakistan's croplands: A data fusion framework and comparative performance analysis - Akash Hussain; Wenting Han; Muhammad Amjad Saleem; Mubashir Ali Ghaffar; Mohsin Ijaz; Wajahat Waseem; Mahmood Hemat; Atiyyah Rafaqat (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Carbonate mineralogy and diagenetic evolution of the Chiltan Limestone, Lower Indus Basin (Pakistan): Geochemical and petrographic insights for reservoir potential - Waqar Ahmad; Mumtaz Ali Khan; Muhammad Raiees Amjad; Mercè Corbella; Mohammad Zafar; Isaac Corral; Hamad-ur-Rahim; Dídac Navarro-Ciurana (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Dual upcycling of waste PET into both the porous support and the Al-MOF filler of thin film nanocomposite nanofiltration membranes - Aroosa Nehal; Aamir Razaq; Asim Laeeq Khan; Muhammad Yasin; Gianluca Viscusi; Giuliana Gorrasi; Mazhar Amjad Gilani; Beenish Shazadi (Journal of Water Process Engineering, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

How geopolitical risks, green finance, and environmental technologies dynamics shape energy trilemma in BRICS economies? - Muhammad Usman; Yongming Huang; Muhammad Sohail Amjad Makhdum; Daniel Balsalobre-Lorente (Energy Policy, 2026)

Zirconia polymorph engineering enables durable and high-performance solid oxide cells - Muhammad Measam Ali; Amjad Hussain; Beom-Su Kwon; Hye-Sung Kim; Jong-Eun Hong; Tak-Hyoung Lim; Seok-Joo Park; Muhammad Zubair Khan; Dong Woo Joh; Rak-Hyun Song (Chemical Engineering Journal, 2026)

Antagonistic effects of PM2.5 and ozone on respiratory morbidity: A multi-pollutant interaction analysis using outpatient data from China's Pearl River Delta - Shui-Yue Lu; Xue-Dan Xu; Dao-Qin Wang; Muhammad Amjad; Guang-Hui Dong; Li-Zi Lin; Hong-Wei Tu (Atmospheric Environment, 2026)

Fenugreek seed extract supplementation: a mitigating strategy against tannery effluent toxicity in Catla catla - Muhammad Amjad; Syed Makhdoom Hussain; Salma Sultana; Shafaqat Ali; Hesham A. Hassanien (Veterinary Research Communications, 2026)

Harnessing the biocontrol potential of Trichoderma: Mechanisms, applications, and future prospects in sustainable crop protection - Muhammad Faiq Irfan; Amjad Ali; Rabia Noor; Aniqa Ijaz; Hamza Rafiq; Faisal Shafiq Mirza (Physiological and Molecular Plant Pathology, 2026)

Integrated optimization of Lantana camara-based biopesticide for Sitophilus granarius control: Chemical profiling, residual efficacy, and machine-learning-driven decision support - Pervin Erdogan; Muhammad Aasim; Zemran Mustafa; Amjad Ali; Seyid Amjad Ali; Rashid Abbas Khan; Abdul Waheed (Journal of Stored Products Research, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

A review on sustainable aviation fuel production via diverse biomass and waste-derived feedstocks and cutting-edge conversion technologies - Wajahat Waheed Kazmi; Muhammad Wasi Syed; Muhammad Waqas; Umair Hassan Bhatti; Ahmed Omer; Mansoor Ali; Zulqarnain; Ishaq Kariim; Amjad Hussain; Faysal M. Al-Khulaifi (Biomass and Bioenergy, 2026)

Spatiotemporal footprints and health risk assessments of odor emissions from large-scale food waste anaerobic digestion plants - Lin Cui; Ziyang Lou; Long Kong; Farooq Muhammad Amjad; Zhijie Wang; Changfu Yang; Jun Si; Meilan Zhang; Luochun Wang; Zhaowen Cheng (Atmospheric Environment, 2026)

Cyclic Use of Wastewater and Canal Water Improves Maize Growth while Reducing Heavy Metal Accumulation in Soil - Shaikh Amjad Salam; Muhammad Qasim; Hossam S. El-Beltagi; Usman Zulfiqar; Mohammed S. Alotaibi; Nozimakhon Khodjimurodova; Kabulzhan Azizov; Nazih Y. Rebouh (Water, Air, & Soil Pollution, 2026)

Trichothecium pseudoroseum sp. nov. (Myrotheciomycetaceae, Hypocreales) From Asia Revealed by Morphology and Multigene Phylogeny - Muhammad Binyamin Khan; Najam‐ul‐Sehar Afshan; Muhammada Jabeen; Muskan Amjad; Sardar Ali; Entaj Tarafder; Samantha C. Karunarathna; Ting Chi Wen (New Zealand Journal of Botany, 2026)
Trichothecium pseudoroseum sp. nov. is described from Yunnan Province, China, and Azad Jammu & Kashmir, Pakistan, based on morphological characteristics and multigene phylogenetic analyses. It is distinguished by its conidiophores, which arise directly from the substrate, are unbranched, solitary, long, slender, septate, slightly curved, smooth‐walled, and hyaline; the conidiogenous cells are smooth, hyaline, located at the apex, slightly swollen, and monoblastic, producing conidia that are ellipsoid, oblong, or pyriform in shape, asymmetrical, one‐septate, and smooth‐walled. To confirm its taxonomic placement, a multigene phylogenetic analysis based on Large Subunit and Internal Transcribed Spacer sequences was conducted, confirming it as an undescribed species and naming it as T. pseudoroseum . The fungus was isolated from the leaves of Trifolium sp., representing the first report of a Trichothecium species on this host. A full description, illustrations, and phylogenetic analysis results for T. pseudoroseum are provided, with comparisons to closely related taxa. This finding extends the known host range of T. pseudoroseum and provides new insights into its biodiversity and interactions with the Trifolium sp.

Comparative identification of abiotic stress-responsive differentially expressed genes in chickpea using unsupervised machine learning, and traditional meta-analysis - Mohammad Shafiq; Rimshah Sabir; Yossma Waheed; Xue Feng; Kirill Sergeeyvich Golokhvast; Muhammad Amjad Nawaz (Genes & Genomics, 2026)

Nano-enabled spray-induced RNA interference against fungal pathogens of oilseed crops: carrier performance, delivery evidence and field translation - Amjad Ali; Sana Hanif; Afifa Azad; Kanza Azad; Tehreem Eraf; Muhammad Aasim; Ashrit Gulfraz; Faheem Shehzad Baloch; Muhammad Shahbaz (World Journal of Microbiology and Biotechnology, 2026)

Selenium and Vitamin E restore redox balance, gut microbiota and reproductive function against cadmium-induced toxicity in male rabbits - Ayesha Gill; Mudasser Habib; Amjad Hameed; Wajid Ishaque; Muhammad Kashif Saleemi; Rida Fatima; Ali Dogan OMUR; Tarique Hussain (Journal of Hazardous Materials, 2026)

Nano-enabled RNAi strategies for sustainable citrus protection against viral pathogens - Amjad Ali; Ameel Riaz; Muhammad Faiq; Jaya Seelan Sathiya Seelan; Faheem Shehzad Baloch; Muhammad Aasim; Muhammad Shahbaz (Planta, 2026)

Immunoinformatics-driven multi-epitope vaccine design as a promising strategy against multidrug-resistant pathogens: a comprehensive review - Rameen Nasir; Muhammad Mutayyab Javaid; Raheen Rahman; Rimsha Abbasi; Muneeb Khalid; Muhammad Arslan; Muhammad Amjad Sajjad; Ahsan Ibrahim (Folia Microbiologica, 2026)

Can baxdrostat redefine blood pressure control in resistant and uncontrolled hypertension? a systematic review, meta-analysis, and trial sequential analysis - Bilal Wazir Khan; Muhammad Yahya; Hamza Wazir Khan; Miguel Alejandro Rivas Perez; Tayyaba Ikram Qazi; Humaira Obaid; Muhammad Mustafa Khan; Muhammad Maaz Amjad; Muhammad Faaz Khan; Aneeq Mahmood Khan; Muhammad Junaid Khan; Sajjad Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Learning the assay, not the hazard: how computational toxicity models inherit the artifacts of their high-throughput training data - Muhammad Javid Iqbal; Tooba Amjad; Cristian Paz (Archives of Toxicology, 2026)

Antimicrobial Plant Protein Patatin: Identification and In-Silico Analysis Through Phylogenetics and Molecular Docking - Sarah Tariq; Binish Khaliq; Hina Shaheen; Ahmad Riaz; Sumaira Rubbani; Muhammad Sajid Hamid Akash; Amjad Hussain; Muhammad Imran; Muhammad Arslan Javed; Ahmed Akrem; Sohaib Mehmood; Sajjad Azam (Agricultural Research, 2026)

Elicitors in Plant Defense: Exploring Their Role in Biotic and Abiotic Stress Resistance - Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Aneeq Ur Rahman; Chidera Anuforo; Asia Maqbool; Amjad Ali; Muhammad Faheem Jan; Muhammad aasim; Heba I. Mohamed; Faheem Shehzad Baloch (Journal of Plant Growth Regulation, 2026)

Comparative in vitro pathogenicity of different oil-based formulations of Metarhizium anisopliae against three different aphid species - Ahmad Nawaz; Anam Ejaz; Tariq Mustafa; Usman Naeem; Amna Irshad; Muhammad Dildar Gogi; Muhammad Tayyib; Muhammad Naveed; Amjad Abbas; Muhammad Jalal Arif (International Journal of Tropical Insect Science, 2026)

Nano-enabled strategies for sustainable management of Fusarium diseases in crops: Mechanism, application and environmental considerations - Amjad Ali; Muhammad Shahbaz; Jaya Seelan Sathiya Seelan (Physiological and Molecular Plant Pathology, 2026)

Inter-device interaction effects on turbine performance and blade loads in axially aligned tidal turbine arrays - Mujahid Badshah; Saeed Badshah; Sajjad Ahmad; Imtiaz Alam Shah; Zia Ur Rehman; Muhammad Amjad; Sakhi Jan (Ocean Engineering, 2026)

PM2.5-bound organophosphate esters and childhood attention-deficit hyperactivity disorder symptoms: A population-based study from China - Chu Chu; Xuan Liu; Yan-Xu Chen; Jia-Xiang Dong; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Xia Liang; Yang Zhou; Muhammad Amjad; Yan Yang (NeuroToxicology, 2026)

Reply to the comment on Zafar et al., 2025: “Retrieving petrogenetic source, compositional diversity and tectono-magmatic scenario of Tethyan sediment-derived magmatic flare-up: A tale from petrochemical and multi-isotopic (Sr–Nd–B–Hf) systematics” by Bhat, 2025 - Tehseen Zafar; Shuguang Song; Hafiz Ur Rehman; Hamed Gamaleldien; Abiola Oyebamiji; Zaheen Ullah; Umar Farooq Jadoon; Muhammad Farhan; Mohamed Zaki Khedr; Irfan Maqbool Bhat; Fatemeh Sepidbar; Fatemeh Nouri; et al. (Gondwana Research, 2026)

In-silico investigation of Agelas marine sponge-derived bioactive compounds as inhibitors of estrogen receptor alpha against breast cancer - Mouzma Amjad; Muhammad Waqas; Aisha Jamshed; Ali Haidar Gormani; Erum Zafar (In Silico Pharmacology, 2026)

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Motorcycle crash injury severity factors in Pakistan: Towards reliable traffic safety policies - Muhammad Junaid; Chaozhe Jiang; Shihan Luo; Amjad Pervez; Jaeyoung Jay Lee (The Social Science Journal, 2026)

Influence of inter-device spacing on performance and blade loads in staggered arrays of tidal current turbines - Mujahid Badshah; Saeed Badshah; Zia Ur Rehman; Sajjad Ahmad; Muhammad Amjad; Sakhi Jan; Imtiaz Alam Shah (Ocean Engineering, 2026)

Protective effects of zinc and Prunus amygdalus against cadmium-induced nephrotoxicity in male Albino rats - Muhammad Talha Ishaq; Faiza Zubair; Naila Riaz; Hira Kanwal; Ayesha Tehreem Shahbaz; Tooba Tahir; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Journal of Trace Elements in Medicine and Biology, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Maize–Soybean Intercropping and Organic Amendments as Sustainable Farming for Higher Productivity, Carbon Sequestration, and Greenhouse Gas Reduction - Sajad Hussain; Du Yongli; Muhammad Shoaib; Sobia Afzal; Hamideh Ghaffari; Fan Yuanfang; Zhang Deyin; Sana ur Rehman; Amjad Saeed; Yang Xinghong; Anshu Rastogi; Marian Brestic (Precision Agriculture, 2026)

Correction to: A study on using custom 3D-printed tongue bites for radiotherapy patients with oral tongue carcinoma - Muhammad Furqan Zulqurnain; Haris Arif; Misbah Batool; Nouman Amjad; Robin Hill (Physical and Engineering Sciences in Medicine, 2026)

A study on using custom 3D-printed tongue bites for radiotherapy patients with oral tongue carcinoma - Muhammad Furqan Zulqurnain; Haris Arif; Misbah Batool; Nouman Amjad; Robin Hill (Physical and Engineering Sciences in Medicine, 2026)
Oral cavity cancers are a debilitating form of head and neck cancer with high rates of mortality. Radiotherapy is one of the main forms of treatment but relies on minimizing doses that are delivered to organs at risk and considering any motion in the mouth. One solution is to use a block within the mouth which acts to reduce motion and decreases tissue heterogeneity. In this work, we developed a process for designing a customized tissue-equivalent 3D-printed tongue bite and evaluated its impact on the radiation treatment. Six patients with stage III or IV oral cancer were involved. Computed tomography (CT) images for each patient were acquired with currently used Styrofoam tongue bites within the mouth. The designs of 3D tongue bites were prepared using those CT images and then printed on an SLA printer using F80 resin which is a tissue-equivalent and biocompatible material. Secondary CT images were then acquired for each patient with the 3D tongue bites to have a dosimetric comparison. Volumetric-modulated arc therapy (VMAT) planning was carried out for individual patients on both CT images. Plan parameters, fractionation scheme and optimization priorities were all kept the same. The radiotherapy plans utilizing 3D tongue bites showed better PTV coverage and reduced D max ( p = 0.028). Doses to organs at risk (OARs) including brainstem, parotid glands and hard palate were also reduced ( p < 0.028) except for the spinal cord ( p > 0.05). The dose conformity and homogeneity were also improved ( p = 0.028 and p = 0.044 respectively). All patients reported that the 3D tongue bites were soft, conformal to the oral cavity, comfortable and did not cause any gag reflex. We conclude that the 3D tongue bite is a useful utility that improves the treatment of patients with oral cancer.

Chemical Profile, Biological Activities, Molecular Docking, and Density Functional Theory (DFT) of Cymbopogon citratus Essential Oil Extracted By Conventional and Superheated Steam Extraction Techniques - Muhammad Adnan Ayub; Fiza Bashir; Khayala Mammadova; Muhammad Talha Anjam; Muhammad Ijaz; Amjad Hussain; Mohamed Fawzy Ramadan; Fahim Arshad; Muhammad Zubair (Journal of Pharmaceutical Innovation, 2026)

Understanding goat production systems in diverse agro-ecological zones under subtropical climate: a farmer-centered survey approach - Amjad Atta; Muhammad Irfan-ur-Rehman Khan; Abdul Rehman; Kamran Ashraf (International Journal of Biometeorology, 2026)

Synergistic biocontrol of Parthenium hysterophorus: the role of Curvularia specifera and Zygogramma bicolorata - Syed Muhammad Ziaullah; Muhammad Hamayun; Amjad Iqbal; Syed Asim; Sajid Ali; Anwar Hussain (Archives of Microbiology, 2026)

Efficacy of aripiprazole and valbenazine in the treatment of tourette syndrome: a systematic review and meta-analysis of randomized controlled trials - Muneeb Ahmad Muneer; Ume Habiba; Shajjia Shehzad; Washija Batool; Dawood Shah; Zain Shahzad; Muhammad Khizar Kirmani; Zohaib Hassan Siddiqui; Areeb Amjad; Ameer Hamza; Muhammad Faizan Khan; Fahad Siddique Butt; et al. (Acta Neurologica Belgica, 2026)

Titanium dioxide nanoparticles as a sustainable strategy to control root-knot nematodes (RKNs) in tomato (Solanum lycopersicum L.) - Asma Mehak; Abida Akram; Amjad Ali; Naveed Iqbal Raja; Tariq Mukhtar; Jaya Seelan Sathiya Seelan; Muhammad Shahbaz (Physiological and Molecular Plant Pathology, 2026)

Perfluorooctane sulfonate (PFOS) induces Caspase-8-mediated pyroptosis via GSDMD and GSDME to drive retinal disease: Evidence from epidemiological and experimental studies - Lu-Yin Wu; Li-Xia Liang; Jia-Xin Zhou; Yun-Ting Zhang; Zeeshan Mohammed; Muhammad Amjad; Yang Zhou; Zhi Wang; Guang-Hui Dong; Wen-Wen Bao (Environmental Pollution, 2026)

Machine learning and design of experiment for enhanced biomass using N2 and CO2-enriched biochar at different pyrolysis temperatures - Muhammad Aasim; Ebubekir Siddik Aydin; Ibrahim Korkut; Başak Temur Ergan; Ahmet Say; Salma Naimatullah Soomro; Sabeen Rehman Soomro; Seyid Amjad Ali; Sezai Ercişli; Ramazan Katırcı (Biomass and Bioenergy, 2026)

Charcoal rot in sesame: infection biology, host resistance mechanism, and genomic-enabled strategies for durable resistance breeding - Amjad Ali; Muhammad Azhar Nadeem; Fatih Ölmez; Cemal Kurt; Faheem Shehzad Baloch (Theoretical and Applied Genetics, 2026)
Sesame ( Sesamum indicum L.) is a globally important oilseed crop, but its production is constrained by charcoal rot, caused by the soil-borne fungus Macrophomina phaseolina. The pathogen’s exceptionally broad host range, long-term soil persistence through microsclerotia, and increased aggressiveness under high temperature and drought make charcoal rot a major destructive constraint in sesame-growing regions. This review integrates current knowledge on the biology, epidemiology, infection processes, and genetic population variability of Macrophomina spp. in relation to charcoal rot development in sesame. We also summarize key host resistance mechanism including pathogen perception, cell wall reinforcement, phenylpropanoid-mediated defense, antioxidant responses, and associated physiological and molecular adaptations. Particular attention is given to the challenges of resistance screening under variable environmental conditions, including heat- and drought-associated disease expression and pathogen diversity, which complicate the identification of stable resistance sources. The review further examines progress in sesame improvement through germplasm characterization, mutation breeding, interspecific introgression, high-throughput phenotyping, and genomic-assisted approaches such as QTL mapping, genome-wide association studies (GWAS), marker-assisted selection, genomic selection, and functional validation. Integrating these tools with multi-omics and gene-editing strategies offers a promising route for accelerating the development of durable, climate-resilient charcoal rot resistance cultivars. Broader use of diverse germplasm, standardized multi-environment phenotyping, and international collaboration will be essential for sustainable resistance breeding and future sesame production.

Impacts of climate change and local stressors on the coral community structure off the eastern coast of Pakistan - Amjad Ali; Azka Rafiq Malik; Naveed Ahmad; Gulab Said; Zulfiqar Ali Mirani; Seema Shafique; Habibul Hassan; Ateeque Rahman Khooharo; Faiz Muhammad (Regional Studies in Marine Science, 2026)

Correction: Assessment of spatial and seasonal variation in soil heavy metal contamination adjacent to Chini Lake, Malaysia - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat‑Ul‑Ain Raza (Environmental Geochemistry and Health, 2026)

Effect of Nitrogen and Maize Straw on Soil Nitrogen Transformation, Farm Profitability, and Wheat Yield: Balancing Productivity and Environmental Sustainability - Siddique Ahmad; Wenjing Song; Yanling Mu; Xiaobin Zhang; Shuping Xiong; Muhammad Arif; Muhammad Amjad; Laiba Urooj; Basit Ullah; Xinming Ma; Yihao Wei (Agricultural Research, 2026)

Biofloc technology: a comprehensive review of its implications for enhancing aquaculture production - Nadia Yasin; Syed Makhdoom Hussain; Bedur Faleh Albalawi; Muhammad Amjad; Adan Naeem; Eman Naeem; Zainab Akram; Mubeena Akbar (Aquaculture International, 2026)

Molecular prevalence, genetic diversity and effect of Toxoplasma gondii infection on the hematological parameters of various bird species - Tauqir Un Nisa; Fatima Mushtaq; Humaira Zulfiqar Ali Gondal; Naila Amjad; Muhammad Usman; Muhammad Ali; Muhammad Latif; Hira Muqaddas; Furhan Iqbal (Biologia, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Eco-engineered silver nanoparticles for multifunctional cotton fabric with integrated UV protection, antimicrobial efficacy and thermal regulation - Muhammad Amjad; Zehan Zeng; Haozhen Li; Ayesha Mohyuddin; Wajad Ulfat; Muhammad Asif Iqbal; Khurmatbek Jumaniyozov; Tonni Agustiono Kurniawan; Xingyi Ma (Chemical Engineering Journal, 2026)

Advances in CRISPR/Cas systems for engineering abiotic stress tolerance in plants: mechanisms and future prospects - Muhammad Farooq; Asma Khan; Amjad Hassan; Mohammad Maroof Shah (Planta, 2026)

Calotropis Leaf Extract-Assisted Phytoextraction of Nickel Contaminated Soils - Muhammad Rizwan Shah; Gulzar Akhtar; Hafiz Nazar Faried; Muhammad Asif Shehzad; Amjad Farooq (Journal of Soil Science and Plant Nutrition, 2026)

Efficient De Novo Assembly and Recovery of Microbial Genomes from Complex Metagenomes Using a Reduced Set of k-mers - Hajra Qayyum; Muhammad Faheem Raziq; Haseeb Manzoor; Syed Shujaat Ali Zaidi; Amjad Ali; Masood Ur Rehman Kayani (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Advancing future drought characterization: a two-phase Bayesian model averaging approach for GCM ensemble calibration - Nosheen Amjad; Muhammad Ismail; Zulfiqar Ali (Applied Geomatics, 2026)

Integrating Conventional and machine learning approaches with seismic inversion for optimized porosity estimation in heterogeneous siliciclastic rocks - Muyyassar Hussain; Urooj Shakir; Zohaib Naseer; Muhammad Raiees Amjad; Farooq Arshad; Muhammad Kamal; Ahmed E. Radwan (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Convergence of Digital Twins and food drying technology: How to bring the next generation of dryers to life!? - Arman Arefi; Carlos Vilas; Mulugeta Admasu Delele; Petra Foerst; Sebastian Gruber; Mohammad Kaveh; Farhad Khoshnam; Norhashila Hashim; Maimunah Mohd Ali; Saman Zohrabi; Muhammad Tayyab; Aditya Parmar; et al. (Journal of Food Engineering, 2026)

Nigella sativa L. (Black cumin) seeds impart protective effects against Staphylococcus aureus induced septic arthritis through the modulation of immune and inflammatory responses - Muhammad Aamir Shaheen; Adeel Sattar; Huma Rao; Amjad Riaz; Abdul Basit (Food Bioscience, 2026)

Fuel-flexible flat-tubular solid oxide fuel cell stack for high performance and durable operation - Muhammad Haseeb Hassan; Saeed Ur Rehman; Syeda Youmnah Batool; Amjad Hussain; Rak-Hyun Song; Tak-Hyoung Lim; Jong-Eun Hong; Dong-Woo Joh; Seok-Joo Park; Hye-Sung Kim; Seung-Bok Lee (Chemical Engineering Journal, 2026)

Development of Kling–Gupta Hybrid Weighted Ensemble for Improving Future Projections of Drought Characterization Under Different Climate Change Scenarios - Nosheen Amjad; Muhammad Ismail; Zulfiqar Ali (Pure and Applied Geophysics, 2026)

Assessment of spatial and seasonal variation in soil heavy metal contamination adjacent to Chini Lake, Malaysia - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat-Ul-Ain Raza (Environmental Geochemistry and Health, 2026)

Virophages: mechanisms, ecological Roles, and therapeutic potential in combating giant virus infections - Muhammad Talha; Mehak Faisal; Amna Mujtaba; Amna Amjad; Nouraiz Abbas; Laiba Shamim; Fakhar e Mahin; Muammar Hassan; Muhammad Daim Hassan; Muhammad Abdur Rehman Awaisi (Archives of Microbiology, 2026)

Biostimulant effect of seaweed extracts on micropropagation of important ground macrophyte Micranthemum tweediei and data-driven insights using machine learning and response surface regression - Esra Özcan; Seyid Amjad Ali; Muhammad Asim; Hasan Hüseyin Atar (Aquaculture International, 2026)
Commercially viable in vitro cultivation of ornamental and aquatic plants depends heavily on the proper use of bio-stimulants that encourage healthy and uniform growth. This study explores the role of two seaweed extracts, Jania rubens and Cystoseira barbata , in promoting in vitro micropropagation of Micranthemum tweediei (Monte Carlo), a widely used aquatic plant. Culture medium was enriched with different concentrations (2.5–20.0%) of J. rubens and C. barbata extracts with 1–4 g L −1 Murashige and Skoog (MS) nutrient media. Considering all results, J. rubens extract was more effective than C. barbata in terms of micropropagation and chlorophyll content of M. tweediei . Addition of 5% J. rubens extract to 2 g L −1 MS medium (approx. half strength) resulted in a 47% increase in clump diameter (5.18 cm), a 173% increase in rooting rate (92.4%), and a 108% increase in shoot clump fresh weight (3.6 g), and 84%, 115%, and 87% increases in chlorophyll a , b , and total chlorophyll levels, respectively, compared to the control 2 g L −1 MS medium without extract. Micropropagation parameters resulting from 4 g L −1 MS (approx. full strength) supplemented with J. rubens extract were lower than those obtained from 2 g L −1 MS. Unlike J. rubens , C. barbata showed the highest micropropagation when 10% extract was added to 4 g L −1 MS nutrient medium, resulting in a clump diameter of 5.11 cm, 42.8% rooting, a fresh clump weight of 7.37 g, and a dry clump weight of 0.59 g. Propagated in vitro plants were easily acclimated to external conditions in aquariums. Results of response surface regression analysis (RSRA) confirmed the results, and MS concentration influenced the plant biomass and chlorophyll contents, whereas seaweed type and concentration regulated the clump diameter and rooting. Application of machine learning models validated and predicted the outcomes precisely. Multi-layer perceptron (MLP) model exhibited superior predictive accuracy for morphological traits, while more predictive accuracy of chlorophyll parameters was attributed to Random Forest (RF) model. This study has shown for the first time that aquatic plants can be micropropagated more successfully and at lower cost by adding seaweed extracts to in vitro nutrient media without the need for growth regulators.

Short dry period improves postpartum energy balance and reproduction but reduces milk yield in dairy cows - Melad Ahmed; Amjad Riaz; Nasim Ahmad; Muhammad Naveed ul Haque; Hifz ul Rahman; Muhammad Yaseen; Talha Ashraf; Muhammad Abdullah; Ali Hassan; Ali Husnain (Theriogenology, 2026)

Evaluating synergistic toxicology effects of mixed microplastics on marine micro crustacean Artemia salina - Mariam Ali; Hira Amjad; Imran Hashmi; Hassan Shafiq; Noreddine Ghaffour; Muhammad Saqib Nawaz (Regional Studies in Marine Science, 2026)

Green synthesis of biodiesel from novel non-edible Quercus baloot Griff seed oil catalyzed by iron-modified clay nanocatalyst - Maryam Naseem; Rozina; Okezie Emmanuel; Mushtaq Ahmad; Mehreen; Amjad Khan; Muhammad Zafar (Next Research, 2026)

Unveiling the charge transfer pathways in CuWO4/NiFe/SnWO4 coupled S-scheme heterojunction for photocatalytic dye degradation - Rimsha Aqeel; Tanveer Hussain Bokhari; Saqib Javaid; Amina Zafar; Muhammad Inayat Ullah; Muhammad Tariq Nadeem; Atia Khalid; Shafqat Karim; Ting Zhu; Amjad Nisar; Mashkoor Ahmad (Journal of Water Process Engineering, 2026)

Southward to northward shifting trends of monsoonal precipitation and their connections with atmospheric circulations over Pakistan: A comparative study of 1961–1990 and 1991–2020 - Sohail Abbas; Amina Ameer; Fenglin Lv; Tingting Li; Yi Chen; Liang Cao; Heli Lu; Yasir Latif; Muhammad Yaseen; Siqi Lu; Wanfu Feng; Amjad Ali Khan (Journal of Hydrology, 2026)

Comparison of the plastisphere and surrounding waste in landfills: Bacterial community assembly and functional evolution - Mengyuan Sun; Long Kong; Muhammad Amjad Farooq; Lei Che; Wangyang Tian; Chuan Wang; Luochun Wang; Ziyang Lou (Journal of Environmental Management, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Electrochemical detection of nitrite ions by solid-state synthesized Au2O3@NiO/ZnO nanocomposite for the environmental safety assessment - Mohammed Muzibur Rahman; Abdulkarim Albishri; Saeed D. Alahmari; Amjad E. Alsafrani; Nouf M. Alourfi; O. Madkhali; Roaa A. Tayeb; Muhammad Fazle Rabbee (Chemical Engineering Journal, 2026)

Fungal endophytes isolated from Withania somnifera Markedly exhibit antitumor activity against human glioblastoma - Arshad Ahmad; Sumera Afzal Khan; Ishaq Nasib Khan; Amjad Iqbal; Muhammad Hamayun (Natural Product Research, 2025)

Future of PARP inhibitors in cancer treatment: overcoming resistance and enhancing efficacy with combination therapies - Muhammad Shoaib; Zeeshan Ahmad Bhutta; Ahsan Javed; Muhammad Nabeel Amjad; Wenzhu Li; Kyung-Chul Choi; Wanxia Pu (Journal of Zhejiang University-SCIENCE B, 2025)

Spatial assessment and ecological risk evaluation of soil heavy metal contamination using multivariate statistical techniques - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat-Ul-Ain Raza; Goh Choo Ta; Sharina Binti Abdul Halim (CATENA, 2025)

Synergistic Arsenic Adsorption by Nano Zero-Valent Iron and Biochar: Batch and Column Scale Performance - Muhammad Asif Naeem; Muhammad Imran; Muhammad Amjad; Ghulam Mustafa Shah; Ghulam Abbas; Behzad Murtaza; Muhammad Shafique Khalid; Hafiz Faiq Bakhat; Samina Khalid; Muhammad Imtiaz Rashid (Water, Air, & Soil Pollution, 2025)

Artificial intelligence-driven validation of silver and titanium nanomaterials impact on morpho-chemical potential of industrial hemp (Cannabis sativa L.) - Ozlem Akgur; Muhammad Aasim; Seyid Amjad Ali (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Unveiling genetic diversity and population structure in lentil (Lens culinaris) germplasm through scot markers - Sarmad Ali Qureshi; Muhammad Azhar Nadeem; Meliha Feryal Sarıkaya; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altafl; Dilek Tekdal; Muhammad Kashif Ilyas; Seyithan Seydoşoğşu; Sezai Ercişli; Kağan Kökten; Faheem Shahzad Baloch (Molecular Biology Reports, 2025)

Molecular Epidemiology and Resistant Gene Mapping of Bacterial Isolates from Houbara bustards - Maham Fatima; Tasleem Kausar; Amjad Islam Aqib; Muhammad Shoaib; Farid S. Ataya; Mohamed Saad Daoud (Current Microbiology, 2025)

The impact of germination time on nutritional and antioxidant properties of selected cereals - Fahid Nazir; Hamza Zahid; Muhammad Riaz; Yahya Mushtaq; Natasha Amjad; Humaira Iqbal; Muhammad Rizwan Majeed; Shazia Kousar; Muhammad Ahmad Mudassir (Cereal Research Communications, 2025)

Optimizing aquaculture sustainability: Microalgae-based co-culture systems for aquaculture wastewater treatment and pollution reduction - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Eman Naeem; Muhammad Amjad; Zeeshan Yousaf; Muhammad Faisal (Algal Research, 2025)

Remedial effects of fenugreek seed extract against tannery effluent toxicity on the growth, blood profile, immune response, and antioxidant activity in Labeo rohita - Muhammad Amjad; Syed Makhdoom Hussain; Salma Sultana; Shafaqat Ali (Aquaculture International, 2025)

Turn-off Fluorimetric Detection of Fe3+ Metal Ions by a Schiff Base Probe (E)-2-(((2-hydroxy-4-sulfonaphthalen-1-yl) imino) methyl) Benzoic Acid: A Combined Experimental and Theoretical Study - Muhammad Shahbaz; Muhammad Aqib Khurshid; Muhammad Ejaz; Mazhar Amjad Gilani; Maham Saeed; Ayesha Shahzad; Sundas Shahzad; Rashid Masih; Shahzad Sharif (Journal of Fluorescence, 2025)

Occurrence and molecular characterization of root-knot nematodes on tunnel-grown cucumber (Cucumis sativus) in Balochistan province of Pakistan - Syed Shams Ullah; Amjad Abbas; Muhammad Dildar Gogi; Shahid Siddique; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

Endophytic fungi as biocontrol agents: A metabolite-driven approach to crop protection and sustainable agriculture - Muhammad Faiq; Amjad Ali; Shazia Shafique; Sobiya Shafique; Allah Rakha Yaseen; Rimsha Fatima; Muhammad Tanveer Altaf; Faheem Shehzad Baloch (Physiological and Molecular Plant Pathology, 2025)

Sustainable hybrid constructed wetland-biological trickling filter system for simultaneous removal of antibiotics and heavy metals: Performance, mechanisms, and microbial insights - Arshad Ameen; Yu Zheng; Qian Wang; Yuanyuan Li; Saleem Ullah Saleem; Muhammad Amjad Saleem; Waqas Niaz; Hannan Ahmad Anjum; Fengmin Li (Journal of Water Process Engineering, 2025)

Recent progress in biomass polymer based hydrogel membranes for adsorption and photocatalytic pollutants removal: fabrication, challenges and future perspectives - Muhammad Usman Hameed; Luqman Ali; Ayesha Ahmad; Pei Zhang; Saleem Raza; Sikandar Khan; Wei-Ren Liu; Zainab Amjad (Desalination, 2025)

Bacillus Inoculation Along with Biogas Slurry Mitigates Nickel Stress in Raphanus Sativus by Regulating Ni Accumulation and the Antioxidant Defense System - Iftikhar Ahmad; Shehzad Mehmood; Muhammad Atif Muneer; Aftab Jamal; Amjad Farooq; Muhammad Farhan Saeed; Qasim Ali; Umar Daraz; Nabil Touzout; Adil Mihoub; Jun Zhou (Water, Air, & Soil Pollution, 2025)

Projecting future climate extremes in the glacier-fed upper indus basin using machine learning based downscaling of CMIP6 GCMs - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Muhammad Ismail; Mubashir Ali Ghaffar; Ahmad Mujtaba; Jinwook Lee; Muhammad Azhar Inam; Arshad Ameen (Theoretical and Applied Climatology, 2025)

Selection criteria for the enhancement of nitrogen use efficiency in wheat using two step association analysis - Muhammad Amjad; Siddique Ahmad; Fahim Ullah Khan; Rafi Ullah; Iltaf Ullah; Muhammad Zahid Shah; Umar Bin Qasim (Vegetos, 2025)

Retraction notice to “Strigolactone decreases cadmium concentrations by regulating cadmium localization and glyoxalase defense system: Effects on nodules organic acids and soybean yield” [Chemosphere 335, September 2023, 139028] - Tariq Shah; Muhammad Asad; Zeeshan Khan; Khadija Amjad; Abdulaziz Abdullah Alsahli; Roberto D'amato (Chemosphere, 2025)

Scenario analysis of Saudi Arabia's residential solar energy incentives - Sikandar Abdul Qadir; Amjad Ali; Md Tasbirul Islam; Muhammad Shahid (Utilities Policy, 2025)

Distinct gonadotropin receptor profiles across follicle sizes reveal potential mechanism for follicular co-dominance in goats - Waqas Ahmad; Muhammad Suleman; Jawad Akhtar; Amjad Riaz; Khalid Javed; Muhammad Imran Rashid; Muhammad Irfan-ur-Rehman Khan (Theriogenology, 2025)

Biobased carbon quantum dots: An emerging nano-enabled paradigm for pesticide removal and sustainable plant protection - Usman Arshad; Dan Chen; Haichao Cao; Chao Feng; Linwei Liu; Muhammad Amjad Ali; Zhang Wanhong; Yishan Li; Lijun Jiang; Jinguang Yang (Science of The Total Environment, 2025)

Machine learning-based streamflow projections in the upper indus basin under CMIP6 climate scenarios - Muhammad Amjad Saleem; Muhammad Shoaib; Sarfraz Hashim; Muhammad Shoaib; Hafiz Umar Farid; Mubashir Ali Ghaffar; Muhammad Ismail; Arshad Ameen; Jinwook Lee; Muhammad Azhar Inam; Changhyun Jun (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

A double-edged sword? Exploring the heterogeneous effects of industrialization, energy efficiency, and disaggregated financial development on environmental management - Zhou Li; Muhammad Usman; Muhammad Sohail Amjad Makhdum; Abdulrahman Alomair (Journal of Environmental Management, 2025)

Evaluation of testicular protective effects of Prunus amygdalus and zinc against cadmium induced toxicity in rats - Ayesha Tehreem Shahbaz; Faiza Zubair; Naila Riaz; Hira Kanwal; Tooba Tahir; Muhammad Talha Ishaq; Nudrat Rafique; Mehwish Perveen; Rabia Irfan; Naila Amjad (Environmental Science and Pollution Research, 2025)

Field-based evaluation of sugarcane bagasse biochar for managing root-knot nematodes in tomato - Maria Fayyaz; Amjad Abbas; Usman Arshad; Farrukh Azeem; Faiz Ahmad Joyia; Abdelaziz Hajjaji; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

Molecular screening of stripe rust and powdery mildew resistance genes in European bread wheat using the validated gene-specific SSR markers - Rada Šućur; Amjad Ali; Parnaz Mortazavi; Velimir Mladenov; Bojan Jocković; Jin Ying Gou; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Yong Suk Chung (Physiological and Molecular Plant Pathology, 2025)

Revisit the role of financial development on economic growth, human development, and sustainable development in higher-income countries - Muhammad Arslan Abdullah; Xiao Han; Muhammad Asif Amjad; Samariddin Makhmudov (Journal of Environmental Management, 2025)

Towards energy efficiency in Pakistan: An analysis of increasing integrated fuel demand using LEAP forecasting and backcasting - Muhammad Shahid; Kafait Ullah; Kashif Imran; Amjad Ali (Fuel, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

Impact of Reconditioning Treatment at Different Temperatures on Potato Cultivars Stored Under Cold Conditions - Adnan Amjad; Aziz Mouhaddach; Hanane Latifi; Rabia Mehboob; Tusneem Kausar; Mohamed Bouhrim; Ramzi A. Mothana; Omar M. Noman; Farzana Siddique; Muhammad Bilal; Shehnshah Zafar; Ashiq Hussain (Potato Research, 2025)

Expression Profiling of Genome-Wide Identified and Characterized Trans-Isoprenyl Diphosphate Synthase Family in Catharanthus roseus (L.) G. Don Under Stress Conditions - Muhammad Huzafa; Amjad Hassan; Batool Bashir; Azhar Mehmood; Jawad Ahmed (Plant Molecular Biology Reporter, 2025)

Empowering Saudi Arabia's sustainable energy future: A LEAP-Based approach for balancing energy supply and demand - Muhammad Shahid; Amjad Ali; Sikandar Abdul Qadir; Md Tasbirul Islam (Utilities Policy, 2025)

Bio-metabolites Mechanism for the Eco-friendly Management of Alternaria Black Spot Disease Through the Use of Bio-agents in Canola - Effat Naz; Muhammad Jabran; Muhammad Bilal; Ikhlas Shafique; Farrukh Azeem; Amjad Abbas; Muhammad Amjad Ali (Journal of Crop Health, 2025)

Precision in vitro propagation by integrating response surface methodology and machine learning for Glossostigma elatinoides (Benth) Hook. F - Esra Özcan; Seyid Amjad Ali; Muhammad Aasim; Hasan Hüseyin Atar (In Vitro Cellular & Developmental Biology - Plant, 2025)
Optimization of in vitro organogenesis of Glossostigma elatinoide s (Benth) Hook. f. was targeted in this study. The experiment was designed with the help of design of experiment (DOE) of response surface methodology (RSM) model. Murashige and Skoog (MS) basal salt, sucrose, and agar were used as input factors and a total of 15 runs were used for optimization. Results were analyzed by ANOVA and response surface regression analysis (RSRA) followed by prediction and validation via different machine learning (ML) models. Results of ANOVA revealed the impact of different combinations on output parameters. Results of RSRA illustrated the relationship between input and output parameters. Pareto chart analysis showed the significant impact of MS on clump diameter, fresh wt., and dry wt. Normal plot analysis illustrated the positive impact of MS on all output parameters and increased proportionally with MS concentration. Results of heatmap and network analysis also demonstrated the significance of MS on all output parameters. Comparison of ML models depicted the better performance of multilayer perceptron (MLP) model for rooting ( R 2 = 0.957), fresh wt ( R 2 = 0.806), and dry wt ( R 2 = 0.812). Conversely, the support vector regression (SVR) model demonstrated superior prediction for clump diameter ( R 2 = 0.809). Among the tested models, the SVR model showed the weakest performance, aside from clump diameter, while LightGBM achieved scores close to those of the RF and MLP models across all metrics. The findings clearly indicate that the adopted protocol is well-suited for the effective commercial propagation of the aquatic G. elatinoides plant.

Evaluating water supply and demand growth in the Gulf Cooperation Council countries: projections and policy implications for sustainable water resources management - Amjad Aliewi; Muhammad Al Rashed; Dalal Sadeqi; Harish Bhandary; Ahmed Sefelnasr; Mohsen Sherif; Ahmed Murad; Dalal Alshamsi; Abdel Azim Ebraheem (Arabian Journal of Geosciences, 2025)

Postharvest Treatment with ZnO and CuO Nanoparticles Improves Fruit Quality and Shelf Life of Guava Fruit - Muhammad Shafique Khalid; Samina Khalid; Noosheen Zahid; Mehdi Maqbool; Akif Safeen; Hafiz Faiq Bakhat; Muhammad Amjad; Behzad Murtaza (Applied Fruit Science, 2025)

Assessment of tomato germplasms for Mi-1.2-mediated resistance to Meloidogyne incognita: Integrating in-silico dynamics and bioinformatic approaches - Adil Zahoor; Zeenat Niaz; Muhammad Jabran; Hira Anwar; Amjad Abbas; Abdul Haseeb; Ghulam Mustafa; Sungmi Sun; Seung Hwan Yang; Muhammad Amjad Ali (Physiological and Molecular Plant Pathology, 2025)

Elucidating the synergistic activity of biocontrol agents in combating Xanthomonas citri pv. malvacearum and promoting of physio-chemical responses in cotton - Usman Arshad; Yaxing Feng; Muhammd Raheel; Waqas Ashraf; Muhammad Amjad Ali; Iqra Naeem; Kexin Liu (Physiological and Molecular Plant Pathology, 2025)

Scalable interlinked hierarchical porous biochar-nanosheets for efficient removal of thallium from aquatic environment - Haitao Ren; Zainab Amjad; Atif Saleem; Muhammad Usman; Kukybayeva Dina; Muhammad Haris; Junkang Guo (Journal of Hazardous Materials, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

The asymmetric impact of energy shortages on sustainable development, human development and economic growth in South Asian countries: The moderating role of globalization - Feng Wang; Tayyaba Rani; Muhammad Asif Amjad (Energy Policy, 2025)

Marine life as a source of anti-prostate cancer agents: an updated overview (2003–2023) - Amjad Hussain; Ammara Sohail; Muhammad Sajid Hamid Akash; Sarosh Iqbal; Kanwal Rehman; Muhammad Imran; Shoaib Khan; Muhammad Adnan Ayub; Daijie Wang; Dildar Ahmed; Mohammed Hadi Ali Al-Jumaili; Maria Bashir; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Differential effects of tomato root exudates on the development of endophytic and pathogenic fungi depend on the foliar application of fungi - Rainaz Parvez; Muhammad Hamayun; Asif Mehmood; Amjad Iqbal; Bokyung Lee; Anwar Hussain (Symbiosis, 2025)

Critical appraisal of “altered white matter architecture in patients with isolated congenital anosmia” - Muhammad Taaha Siddiqui; Nawal Fatima; Eman Fatima; Maryam Amjad; Mahnoor Khan (Brain Structure and Function, 2025)

Petrogenesis and tectonic implications of Paleozoic S-type granitic gneisses of Nanga Parbat Syntaxis, North Pakistan - Amjad Hussain; Kui-Dong Zhao; Delores M. Robinson; Sakine Moradi; Muhammad Sajid; Hafiz U. Rehman; Qian Li; Syed Mumtaz Hussain; Rahat Ali; Syed Asim Hussain (Lithos, 2025)

Spatio-temporal distribution, diet and human conflict of snow leopard (Panthera uncia) in the Khunjerab National Park, Gilgit Baltistan - Saira Akber; Tariq Mahmood; Tahir Mehmood; Amjad Rashid Kayani; Muhammad Sajid Nadeem; Faraz Akrim (Food Webs, 2025)

Exploring the potential of novel feedstock (Caesalpinia bonduc seeds) for circular biodiesel production using seed shell-derived green nanocatalysts - Roshan Amjad; Mushtaq Ahmad; Shazia Sultana; Mamoona Munir; Muhammad Ishtiaq Ali; Mohamed M. El-Toony; Nizomova Maksuda Usmankulovna; Burkhan Avutkhanov; Ahmad Mustafa (Biomass and Bioenergy, 2025)

Assessing the Role of Biostimulants in Affecting the Production of Radish and Eggplant - Muhammad Amjad Bashir; Qurat-Ul-Ain Raza; Abdur Rehim; Hafiz Muhammad Ali Raza; Asad Ismail Noor; Mir Sujaul Islam; Faiz-Ul-Hassan; Muhammad Zafar-Ul-Hye; Yucong Geng (Journal of Soil Science and Plant Nutrition, 2025)

Integrated Management of Nitrogen and Spent Mushroom Compost for Improved Wheat Yield and Soil Fertility - Uzair Ahmed; Aftab Jamal; Waleed Iqbal; Durrishahwar; Usama Qayyum; Muhammad Farhan Saeed; Amjad Ali; Domenico Ronga; Yaser Hassan Dewir; Jakub Černý (Journal of Soil Science and Plant Nutrition, 2025)

Combined Application of Compost and Biogas Residues Reduces Soil and Pore Water Metal Concentration and Their Residual Toxicity to Wheat Seedlings - Iftikhar Ahmad; Ghulam Mustafa Shah; Hafiz Muhammad Shahbaz; Aftab Jamal; Muhammad Imtiaz Rashid; Muhammad Farhan Saeed; Amjad Farooq; Qasim Ali; Domenico Ronga (Journal of Soil Science and Plant Nutrition, 2025)

Genetic diversity in wheat landraces for agronomic traits and yellow rust resistance - Shamim Khan; Niaz Ali; Fahim Ullah Khan; Israr Ud Din; Muhammad Amjad; Israr Ahmad (Genetic Resources and Crop Evolution, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Diagenetic heterogeneities in the Jurassic Samana Suk Formation, Foreland Sedimentary Fold and Thrust Belt, Pakistan: an integrated approach for reservoir behavior - Waqar Ahmad; Mumtaz Ali Khan; Muhammad Raiees Amjad; Mohammad Zafar; Mercè Corbella; Dídac Navarro-Ciurana; Hamad ur Rahim (Carbonates and Evaporites, 2025)

Meta-analysis of RNA-seq data of soybean under heat, water, and drought stresses - Mohammad Shafiq; Farrukh Azeem; Yossma Waheed; Igor Eduardovich Pamirsky; Xue Feng; Kirill Sergeeyvich Golokhvast; Muhammad Amjad Nawaz (Plant Biotechnology Reports, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

Retrieving petrogenetic source, compositional diversity and tectono-magmatic scenario of Tethyan sediment-derived magmatic flare-up: A tale from petrochemical and multi-isotopic (Sr–Nd–B–Hf) systematics - Tehseen Zafar; Shuguang Song; Hafiz Ur Rehman; Hamed Gamaleldien; Abiola Oyebamiji; Zaheen Ullah; Umar Farooq Jadoon; Muhammad Farhan; Mohamed Zaki Khedr; Irfan Maqbool Bhat; Fatemeh Sepidbar; Fatemeh Nouri; et al. (Gondwana Research, 2025)

Ostrich oil evaluation; Parallel to food and pharmaceutical industries requirements: A review - Shehnshah Zafar; Adnan Amjad; Muhammad Tauseef Sultan; Muhammad Mueed Tanveer Malik (Food and Humanity, 2025)

Ecotoxicological investigation of arsenic contamination within the water-soil-fruit-human continuum - Muhammad Shafique Khalid; Nimra Farooq; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Samina Khalid; Hafiz Faiq Bakht; Ghulam Mustafa Shah; Muhammad Asif Naeem; Ghulam Abbas; Behzad Murtaza (Environmental Geochemistry and Health, 2025)

Risk assessment of potentially toxic elements, microplastics, and microorganisms in groundwater around municipal solid waste landfill - Xueya Li; Tianmu Peng; Linyi Lin; Muhammad Amjad Khan; Shurui Zhang; Meijuan Kuang; Jinming Lou; Jiaxin He; Pangxiang Zhang; Xiaomao Song; Xu Wang; Qing Huang (Journal of Hazardous Materials, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

Recent progress in 2D-MXene-based membranes for water treatments; fabrication, properties, and advanced desalination application - Muhammad Usman Hameed; Zainab Amjad; Basem Al Alwan; Atef El Jery; Hassan M.A. Hassan; Luqman Ali; Ayesha Ahmad; Sikandar Khan; Saleem Raza (Desalination, 2025)

Effect of GnRH administration on follicular development and ovulation during the early luteal phase in subtropical goats - Waqas Ahmad; Muhammad Irfan-ur-Rehman Khan; Amjad Riaz; Khalid Javed (Domestic Animal Endocrinology, 2025)

Arsenic speciation in soil from urban recreational parks and human health risk assessment - Muhammad Amjad Khan; Javed Nawab; Tasneem Sarwar; Anwarzeb Khan; Iqbal Ahmad; Muhammad Waqas; Shah Nawaz Khan; Mehboob Alam; Kalsoom Kalsoom; Muhammad Ziad; Sardar Khan (Urban Ecosystems, 2025)

Biochemical investigation of FOXP3 genetic polymorphism and its association with biochemical parameters in pre-eclampsia patients - Muhammad Sajid Hamid Akash; Francis Victor; Kanwal Rehman; Amjad Hussain; Mudassar Shahid; Asif Shahzad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Palynological diversity in the Rosaceae flora of Northern Khyber Pakhtunkhwa, Pakistan - Muhammad Abdullah; Mushtaq Ahmad; Zahid Ullah; Amjad Khan; Shabir Ahmad; Hussain Shah; Ateef Ullah; Mohammad Abul Farah; Okezie Emmanuel; Rashid Iqbal; Abduraimov Ozodbek; Maxmudov Azizbek; et al. (Genetic Resources and Crop Evolution, 2025)

Advancing Chickpea Breeding: Omics Insights for Targeted Abiotic Stress Mitigation and Genetic Enhancement - Muhammad Tanveer Altaf; Waqas Liaqat; Amjad Ali; Amna Jamil; Muhammad Fahad; Muhammad Aneeq Ur Rahman; Faheem Shehzad Baloch; Heba I. Mohamed (Biochemical Genetics, 2025)

Highly efficient phosphate extraction from water using bio-composites of nano zero valent iron supported on orange peel powder (nZVI@OPP): performance evaluation and mechanistic insights - Fahad Nadeem; Muhammad Ali Inam; Rashid Iftikhar; Safi Ullah Gill; Hira Amjad (Environmental Science and Pollution Research, 2025)

A new feature selection algorithm combining genetic algorithm, exponential decay function, and machine learning to realize hyperspectral estimation of winter wheat leaf area index - Chenbo Yang; Juan Bai; Hui Sun; Rutian Bi; Lifang Song; Amjad Muhammad; Chao Wang; Yu Zhao; Wude Yang; Lujie Xiao; Meijun Zhang; Xiaoyan Song; et al. (Computers and Electronics in Agriculture, 2025)

Integrated rice-crab co-culture system shows capability to reduce greenhouse gases emission and global warming potential - Muhammad Amjad Bashir; Yang Xu; Hongyuan Wang; Yibin Zhang; Qurat-ul-Ain Raza; Wentao Sun; Muhammad Aon; Xiushuang Zhang; Abdur Rehim; Hongbin Liu (Aquaculture, 2025)

Effect of human chorionic gonadotropin on oocyte maturation and developmental competence in buffalo - Muhammad Bilal; Muhammad Kamran Ashraf; Talha Ashraf; Muhammad Yaseen; Ali Husnain; Muhammad Bilal Bin Majeed; Muhammad Imran; Burhan E. Azam Rana; Muhammad Hassan Mushtaq; Amjad Riaz (Theriogenology, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

Retraction notice to “Alleviation of microplastic toxicity in soybean by arbuscular mycorrhizal fungi: Regulating glyoxalase system and root nodule organic acid” [J. Environ. Manag. 349 (2024) 119377] - Zeeshan Khan; Tariq Shah; Muhammad Asad; Khadija Amjad; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Environmental Management, 2025)

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Effect of resveratrol on post-thaw motility, kinematics, structural parameters and antioxidant/oxidant status of Kamori buck spermatozoa - Tarique Hussain; Muhammad Hammad Fayyaz; Amjad Hameed; Syed Murtaz Hassan Andrabi; Rehana Kausar; Yasin Mubashir; Iqra Batool; Muhammad Shahzad; Ali Dogan Omur (Cryobiology, 2025)

Unveiling the future: Breakthroughs and innovations in MXene-based electrochemical sensors - Muhammad Khan; Xiaohui Sun; Faisal Attique; Muhammad Tahir Saleh; Naveed Ahmad; Kainat Atiq; Muhammad Shafi; Inas A. Ahmed; Imad Barsoum; Muhammad Shahbaz Rafique; Azeem Ullah; Amjad Hussain; et al. (Chemical Engineering Journal, 2025)

Impacts of Conservation Tillage on Agricultural Land Development: A Review - Xue Liang; Sana Ur Rehman; Wang Zhiqi; Muhammad Ali Raza; Imran Haider; Muhammad Hayder Bin Khalid; Amjad Saeed; Zafar Iqbal; Shroz Fatima; Ayesha Siddiqa; Muhammad Ansar; Shahzada Sohail Ijaz; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Biohydrogen and biomethane production from biomass gasification: Compositional analysis, recent advancements, challenges, and prospects - Ahmad Naquash; Zeeshan Hameed; Muhammad Abdul Qyyum; Zakir Khan; Ala’a H. Al-Muhtaseb; Amjad Riaz; Moonyong Lee (Process Safety and Environmental Protection, 2025)

Paleocene Katisho ultramafic-mafic-intermediate igneous rocks in the Ladakh Batholith, northern Pakistan: Implications for the transition from intra-oceanic to Andean type arc setting - Zahid Hussain; Chuan-Lin Zhang; Masumeh Sargazi; Irfan Maqbool Bhat; Xian-Tao Ye; Zhi-Hao Song; Muhammad Farhan; Zaheen Ullah; Tehseen Zafar; Amjad Hussain; Syed Asim Hussain (Lithos, 2025)

Chemistry, biosynthesis, and theranostics of antioxidant flavonoids and polyphenolics of genus Rhododendron: an overview - Amjad Hussain; Sajjad Azam; Rabia Maqsood; Riaz Anwar; Muhammad Sajid Hamid Akash; Hidayat Hussain; Daijie Wang; Muhammad Imran; Katarzyna Kotwica-Mojzych; Shoaib Khan; Shabbir Hussain; Muhammad Adnan Ayub (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Systematic implication of trichome morphology in alpine flora from Hindukush Mountain range - Muhammad Abdullah; Zahid Ullah; Syed Muhammad Iqbal Shah; Mushtaq Ahmad; Amjad Khan; Hussain Shah; Ateef Ullah; Shabir Ahmad; Mohammed Fahad Albeshr; Okezie Emmanuel; Hameed Ullah; Rahman Ali Khan (Genetic Resources and Crop Evolution, 2025)

In Silico Comparison of WRKY Transcription Factors in Wild and Cultivated Soybean and Their Co-expression Network Arbitrating Disease Resistance - Muhammad Amjad Nawaz; Hafiz Kashif Khalil; Farrukh Azeem; Muhammad Amjad Ali; Igor Eduardovich Pamirsky; Kirill S. Golokhvast; Seung Hwan Yang; Rana Muhammad Atif; Gyuhwa Chung (Biochemical Genetics, 2025)

Next-generation vaccines for influenza B virus: advancements and challenges - Muhammad Awais Ashraf; Muhammad Asif Raza; Azka Imran; Muhammad Nabeel Amjad (Archives of Virology, 2025)

Effects of Tribulus terrestris extract and 17 α-methyl testosterone on masculinization, growth, economic efficiency and health assessment of Nile tilapia (Oreochromis niloticus) - Habib Ul Hassan; Amjad Ali; Basim S. A. Al Sulivany; Muhammad Kabir; Roohi Kanwal; Mohammad Z. Ahmed; Rizwana Abdul Ghaffar; Meer Zeeshan Ijaz; Naseem Rafiq; Mary Mahwish; Mohammad Abdul Momin Siddique (Aquaculture International, 2025)

Applicability of Ni@ZnO polymer nanocomposite as an adsorbent for removal of methylene blue dye from synthetic wastewater: Batch studies and multilinear regression (MLR) modeling - Nazish Jabeen; Tanzeela Gulab Shahzady; Ayesha Mohyuddin; Muhammad Amjad; Fatima Batool; Wajad Ulfat; Shabbir Hussain; Hui Hwang Goh; Tonni Agustiono Kurniawan (Environmental Monitoring and Assessment, 2025)

Application of fertilizers improves cadmium phytoextraction efficiency of Nasturtium officinale R.Br. grown in cadmium-contaminated water - Amjad Ali; Niaz Ali; Yansheng Gu; Nisar Ahmad; Nasar Ali; Israr Ahmad; Ajab Khan; Muhammad Anas; Hamad Ur Rehman; Asmat Ali; Muhammad Inayat Ullah khan (Environmental Monitoring and Assessment, 2025)

Accuracy assessment of potential alternatives to observed precipitation for extremes over complex topography - Muhammad Amjad; Naeem Shahzad; Wajeeh Ul Hassan (Theoretical and Applied Climatology, 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

Allelic variation in major genes and quantitative trait loci associated with grain number in historical spring wheat cultivars - Muhammad Aamir Khan; Yuanyuan Tian; Humaira Qayyum; Benish Iltaf; Youshaa Danyal; Muhammad Amjad Farooq; Muhammad Kashif Ilyas; Zahid Mahmood; Shoaib-ur-Rehman; Jindong Liu; Awais Rasheed (Genetic Resources and Crop Evolution, 2025)

A study on the performance of enhancing environmental protection from molecular iodine using granular impregnated activated carbon - Talhat Yaqoob; Masroor Ahmad; Attaullah Shah; Amjad Farooq; Farman Ali; Sahid Mehmood; Sidra Shaoor Kiani; Muhammad Asim Irshad; Azeem Bibi; Naseem Irfan (Environmental Science and Pollution Research, 2024)

Effective synergism of Moringa oleifera with antibiotics, body growth, and decoction replacement - Qandeel Ashraf; Amjad Islam Aqib; Hamid Majeed; Shahbaz Ul Haq; Muhammad Farrukh Nisar; Muhammad Usman; Afshan Muneer; Saba Batool; Farid S. Ataya (South African Journal of Botany, 2024)

A robust and simple non-enzymatic electrochemical sensor based on carbon dots-metal oxide composite for the detection of metronidazole traces in food products - Hafiza Khadija Aslam; Sehrish Bilal; Sana Mir; Sobia Tabassum; Mazhar Amjad Gilani; Mustansara Yaqub; Muhammad Asim (Food Chemistry, 2024)

Dairy farm waste: A potential reservoir of diverse antibiotic resistance and virulence genes in aminoglycoside- and beta-lactam-resistant Escherichia coli in Gansu Province, China - Muhammad Shoaib; Minjia Tang; Amjad Islam Aqib; Xuejing Zhang; Zhongyong Wu; Yang Wen; Xiao Hou; Jinpeng Xu; Ruochen Hao; Shengyi Wang; Wanxia Pu (Environmental Research, 2024)

Socio-economic benefits and policy implications of generating sustainable energy from municipal solid waste in Pakistan - Waqas Ahmad; Muhammad Hassan; Shah Fahad Bin Masud; Muhammad Saad Amjad; Fatin Samara; Zeshan; Mustafa Anwar; Muhammad Zeeshan Rafique; Tahir Nawaz (Energy and Climate Change, 2024)

Detection of extended-spectrum beta-lactamase genes among Escherichia coli isolates of buffalo mastitis milk - Sarang Mazhar Abro; Jam Kashif Sahito; Abdul Ahad Soomro; Amjad Hussain Mirani; Muhammad Azhar Memon; Nazeer Hussain Kalhoro (Ecological Genetics and Genomics, 2024)

Phosphate-solubilizing fungus (PSF) - mediated phosphorous solubilization and validation through Artificial intelligence computation - Fatih Ölmez; Zemran Mustafa; Şahimerdan Türkölmez; Aslıhan Esra Bildirici; Seyid Amjad Ali; Muhammad Aasim (World Journal of Microbiology and Biotechnology, 2024)

Sirtuin insights: bridging the gap between cellular processes and therapeutic applications - Shagufta Kamal; Sharon Babar; Waqas Ali; Kanwal Rehman; Amjad Hussain; Muhammad Sajid Hamid Akash (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

Real-time expression and in silico characterization of pea genes involved in salt and water-deficit stress - Muhammad Farooq; Rafiq Ahmad; Muhammad Shahzad; Saad Ur Rehman; Yasar Sajjad; Amjad Hassan; Mohammad Maroof Shah; Amber Afroz; Sabaz Ali Khan (Molecular Biology Reports, 2024)

Exploring Marine Cloud Brightening with a Reduced Complexity Model - Muhammad Mueed Khan; Christopher Runyan; Shahzad Bashir; Abdul Basit Amjad (Journal of Meteorological Research, 2024)
Throughout the industrial period, anthropogenic aerosols have likely offset approximately one-third of the warming caused by greenhouse gases. Marine cloud brightening aims to capitalize on one aspect of this phenomenon to potentially mitigate global warming by enhancing cloud reflectivity through adjustments in cloud droplet concentration. This study employs a simplified yet comprehensive modeling framework, integrating an open-source parcel model for aerosol activation, a radiation transport model based on commercial computational fluid dynamics code, and assimilated meteorological data. The reduced complexity model addresses the challenges of rapid radiation transfer calculations while managing uncertainties in aerosol–cloud-radiation (ACR) parameterizations. Despite using an uncoupled ACR mechanism and omitting feedback between clouds and aerosols, our results closely align with observations, validating the robustness of our assumptions and methodology. This demonstrates that even simplified models, supported by parcel modeling and observational constraints, can achieve accurate radiation transfer calculations comparable to advanced climate models. We analyze how variations in droplets size and concentration affect cloud albedo for geoengineering applications. Optimal droplet sizes, typically within the 20–35-µm range, significantly increase cloud albedo by approximately 28%–57% across our test cases. We find that droplets transmit about 29% more solar radiation than droplets. Effective albedo changes require injection concentrations exceeding background levels by around 30%, diminishing as concentrations approach ambient levels. Considerations must also be given to the spray pattern of droplet injections, as effective deployment can influence cloud thickness and subsequently impact cloud albedo. This research provides insights into the feasibility and effectiveness of using a reduced complexity model for marine cloud brightening with frontal cyclone and stratus cumulus clouds, and emphasizes the need to also consider background droplets size and concentration than just meteorological conditions.

Evaluation of morphological and biochemical variations in peas under two widespread abiotic stresses - Muhammad Farooq; Rafiq Ahmad; Muhammad Shahzad; Khalid Ahmad; Yasar Sajjad; Amjad Hassan; Abdul Nazir; Mohammad Maroof Shah; Bibi Kalsoom; Sabaz Ali Khan (Acta Physiologiae Plantarum, 2024)

Bioactivities of natural product geodin congeners and their preliminary structure activity relationship - Gulab Said; Amjad Ali; Muhammad Umair; Farooq Ahmad; Salma Gul; Muhammad Ateeq (Natural Product Research, 2024)

Data-driven exploration in complex basins: A critical aspect of new prospect delineation in thin sands using simultaneous seismic inversion - Urooj Shakir; Aamir Ali; Muyyassar Hussain; Ahmed E Radwan; Ahmed Abd El Aal; Muhammad Raiees Amjad; Muhammad Fahad Mahmood (Journal of Earth System Science, 2024)

Nitrous oxide emissions and soil profile responses to manure substitution in the North China Plain drylands - Zhen Wang; Jungai Li; Hongyuan Wang; Bingqian Fan; Muhammad Amjad Bashir; Fuyue Dai; Limei Zhai; Hongbin Liu (Science of The Total Environment, 2024)

Highly efficient adsorptive removal of phosphate using novel perovskite lanthanum ferrite/graphene oxide (LaFeO3-GO) hybrids from water - Jawad Rauf; Muhammad Ali Inam; Rashid Iftikhar; Hira Amjad; Deedar Nabi; Waleed Usmani (Journal of Water Process Engineering, 2024)

A multi-sensor drought index for improved agricultural drought monitoring and risk assessment in the heterogeneous landscapes of the China–Pakistan Economic Corridor (CPEC) - Muhammad Ismail; Yi Li; Ben Niu; Mubashir Ali Ghaffar; Muhammad Amjad Saleem; Kadambot H.M. Siddique (Atmospheric Research, 2024)

Innovative strategies for characterizing and managing huanglongbing in citrus - Mustansar Mubeen; Amjad Ali; Yasir Iftikhar; Muhammad Shahbaz; Muhammad Irfan Ullah; Md. Arshad Ali; Noor Fatima; Jaya Seelan Sathiya Seelan; Yee Shin Tan; Uthman Balgith Algopishi (World Journal of Microbiology and Biotechnology, 2024)

RNA interference: a promising biotechnological approach to combat plant pathogens, mechanism and future prospects - Amjad Ali; Muhammad Shahbaz; Fatih Ölmez; Noor Fatima; Ummad Ud Din Umar; Md. Arshad Ali; Muhammad Akram; Jaya Seelan Sathiya Seelan; Faheem Shehzad Baloch (World Journal of Microbiology and Biotechnology, 2024)

Hydro-geochemistry and age-dependent health risk assessment of nitrate, nitrite, and fluoride in health facilities water: a multivariate analysis - Areej Nadeem; Behzad Murtaza; Muhammad Imran; Muhammad Shafique Khalid; Muhammad Shahid; Abdullah Ghardan Al-Sehemi; Yasar Nelliyot Kavil; Muhammad Amjad; Muhammad Wakeel (Environmental Science and Pollution Research, 2024)

From farm to function: Exploring new possibilities with jute nanocellulose applications - Amjad Farooq; Syed Rashedul Islam; Md. Al-Amin; Mohammed Kayes Patoary; Md Tanjim Hossain; Muhammad Tauseef Khawar; Zongqian Wang; Mingwei Tian (Carbohydrate Polymers, 2024)

Green synthesis of silver nanoparticles for antifungal activity against tomato fusarium wilt caused by Fusarium oxysporum - Raja Zaheer Tabassum; Ansar Mehmood; Abd ur Rehman Khalid; Khawaja Shafique Ahmad; Muhammad Abdul Rauf Khan; Muhammad Shoaib Amjad; Muhammad Raffi; Gull-e-laala Khan; Amna Mustafa (Biocatalysis and Agricultural Biotechnology, 2024)

Deciphering fungicide resistance in Phytophthora: mechanisms, prevalence, and sustainable management approaches - Syed Atif Hasan Naqvi; Muhammad Farhan; Muhammad Ahmad; Rafia Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (World Journal of Microbiology and Biotechnology, 2024)

Nematicidal Potential of Enzymatic Extracts of Pseudomonas aeruginosa and Bacillus cereus on Different Stages of Potato Cyst Nematode Globodera pallida - Abdelaziz Hajjaji; Ghita Ibnchekh; Taha Chouati; Bahia Rached; Muhammad Amjad Ali; Naima Rhallabi; Rajaa Ait Mhand; Fouad Mellouki (Journal of Crop Health, 2024)

Genetic Association Among Morpho-Physiological Attributes Against Heat Tolerance in Rice Genotypes - Hafiz Ghulam Muhu-Din Ahmed; Noor Fatima; Yawen Zeng; Muddassir Hussain; Muhammad Moaaz Mushtaq; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Adnan Noor Shah; Hayssam M. Ali; Mohamed M. A. Abdelhamid; Sezai Ercisli (Journal of Crop Health, 2024)

Effect of supplementing epinephrine in maturation media on in-vitro developmental competence of cattle and buffalo oocytes - Abdul Khaliq; Muhammad Ameer Hamza; Talha Ashraf; Ali Husnain; Muhammad Yaseen; Abdul Rehman; Muhammad Binyameen; Muhammad Yasir Zahoor; Amjad Riaz (Theriogenology, 2024)

Prediction of Nili-Ravi buffalo bull fertility through Fourier harmonic analysis of sperm - Javeria Arshad; John J. Parrish; Muhammad Amjad Awan; Bushra Allah Rakha; Muhammad Waseem; Muhammad Sheeraz Ahmad; Sajid Iqbal; Shamim Akhter (Theriogenology, 2024)

Recent advances in the detection and quantification of manufactured nanoparticles (MNPs) in complex environmental and biological matrices - Qumber Abbas; Muhammad Zia-ur-Rehman; Habib Ullah; Mehar Ahmed Mujtaba Munir; Muhammad Ubaid Ali; Amjad Ali; Krzysztof Pikon; Balal Yousaf (Journal of Cleaner Production, 2024)

Sustainability and photocatalytic performance of MOFs: Synthesis strategies and structural insights - Zeshan Ali Sandhu; Umme Farwa; Muhammad Danish; Muhammad Asam Raza; Aqib Talib; Hifza Amjad; Rukhmah Riaz; Abdullah G. Al-Sehemi (Journal of Cleaner Production, 2024)

Effect of naringenin on post-thaw quality, fertility-associated gene expression and fertilization potential of buffalo (Bubalus bubalis) bull sperm - Ghulam Shabbir Khan; Muhammad Zahid Tahir; Muhammad Yasir Zahoor; Hifz-ul-Rahman; Amjad Riaz (Cryobiology, 2024)

Responsive aerogels of ultra-light flexibility and Fouling-Resistant characteristics to safeguarding X-ray exposure - Bianjing Sun; Tao Wang; Chenchen Qin; Muhammad Amjad Majeed; Zhipeng Wang; Fengyan Tan; Lingling Sun; Xiaokun Wang; Jingyi Zhao; Yong Xue; Chuntao Chen; Dongping Sun (Chemical Engineering Journal, 2024)

Frontiers in bacterial-based green synthesized nanoparticles (NPs): A sustainable strategy for combating infectious plant pathogens - Amjad Ali; Muhammad Aasim; Kübra Çelik; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Biocatalysis and Agricultural Biotechnology, 2024)

Integrated Application of Micronutrients Improves Productivity and Seed Quality of Canola Crop under Conventional Tillage System - Muhammad Ijaz; Shahbaz Khan; Sami Ul-Allah; Abdul Sattar; Ahmad Sher; Muhammad Nawaz; Amjad Hussain; Afroz Rais; Safia Gul; Danish Ibrar; Manzer H. Siddiqui; Abdel-Rhman Z. Gaafar; et al. (International Journal of Plant Production, 2024)

Vermi-remediation impacts on growth and metals bioaccumulation in tomato irrigated with wastewater - Mehboob Alam; Anwarzeb Khan; Rasheeqa Zaman; Shahnawaz Khan; Muhammad Amjad Khan; Imran Ahmad; Abdullah Jalal; Ki In Kim (Chemosphere, 2024)

Correction to: Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)

Exploring Host Resistance and Character Association in Diverse Cotton Germplasm to Manage Cotton Leaf Curl Disease (CLCuD) at Two Hotspots in Punjab, Pakistan - Asia Batool; Jehanzeb Farooq; Muhammad Jabran; Amjad Abbas; Muhammad Amjad Ali (Journal of Crop Health, 2024)

Stripe rust resistance gene Yr15 in Turkish and Kazakhstan wheat germplasms and the potential of Turkish wild emmer for stripe rust breeding - Faheem Shehzad Baloch; Amjad Ali; Daniyar Tajibayev; Muhammad Azhar Nadeem; Fatih Ölmez; Hüsnü Aktaş; Ahmad Alsaleh; Gönül Cömertpay; Mustafa Imren; Zemran Mustafa; Abdelfattah A. Dababat; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2024)

Zeugodacus fruit flies (Diptera: Tephritidae) host preference analysis by machine learning-based approaches - Naila Nazir; Sehar Fatima; Muhammad Aasim; Faheem Yaqoob; Khalid Mahmood; Seyid Amjad Ali; Shahid Iqbal Awan; Ihsan ul Haq (Computers and Electronics in Agriculture, 2024)

Synergizing LED Technology and Hydropriming for Intelligent Modeling and Mathematical Expressions to Optimize Chickpea Germination and Growth Indices - Muhammad Aasim; Fatma Akin; Seyid Amjad Ali (Journal of Plant Growth Regulation, 2024)
The influence of hydropriming and Light Emitting Diodes (LED) on germination and growth indices, followed by optimizing and validation via artificial intelligence-based models was carried out in this research. White LEDs (W-LEDs) were more effective by yielding the most effective growth indices, such as mean germination time (MGT) (1.11 day), coefficient of variation of germination time (CV t ) (20.72%), mean germination rate (MR) (0.81 day −1 ), uncertainty ( U ) (0.40 bit), and synchronization ( Z values) (0.79); the optimum MGT (1.09 day), CV t (15.97%), MR (0.77 day −1 ), U (0.32 bit), and Z (0.55) values were found after 2 h of hydropriming, which was responsible for all efficient growth indicators. W-LEDs with 1 h hydropriming proved to be the ideal LED and hydropriming combination. Results on growth indices for in vitro seedlings were completely different from those on germination indices, and the most desirable germination indices were linked to red LEDs (R-LEDs). Whereas 4 h hydropriming was most effective for the post-germination process. Pareto charts, normal plots, contour plots, and surface plots were created to optimize the input variables. Finally, the data were predicted using Arificial Neural Network (ANN) inspired multilayer perceptron (MLP) and machine learning-based random forest (RF) algorithms. For both models, plant height was correlated with maximum R 2 values. Whereas, all output variables had relatively low mean absolute error (MAE), mean square error (MSE), and mean absolute percentage error (MAPE) scores, indicating that both models performed well. The results of this investigation disclosed a link between certain LEDs and hydropriming treatment for in vitro germination indices and plant growth. Graphical Abstract Graphical presentation of actual and predicted values for germination indices in chickpea

Global nexus between tourism and sustainable futures: the role of economic growth, globalization and renewables - Lixia Gao; Qamar Ali; Muhammad Rizwan Yaseen; Muhammad Sohail Amjad Makhdum; Samuel Asumadu Sarkodie; Madeeha Nisa; Muhammad Tariq Iqbal Khan (Environment, Development and Sustainability, 2024)

A unified framework of response surface methodology and coalescing of Firefly with random forest algorithm for enhancing nano-phytoremediation efficiency of chromium via in vitro regenerated aquatic macrophyte coontail (Ceratophyllum demersum L.) - Seyid Amjad Ali; Numan Emre Gümüş; Muhammad Aasim (Environmental Science and Pollution Research, 2024)
Nano-phytoremediation is a novel green technique to remove toxic pollutants from the environment. In vitro regenerated Ceratophyllum demersum (L.) plants were exposed to different concentrations of chromium (Cr) and exposure times in the presence of titania nanoparticles (TiO 2 NPs). Response surface methodology was used for multiple statistical analyses like regression analysis and optimizing plots. The supplementation of NPs significantly impacted Cr in water and Cr removal (%), whereas NP × exposure time (T) statistically regulated all output parameters. The Firefly metaheuristic algorithm and the random forest (Firefly-RF) machine learning algorithms were coalesced to optimize hyperparameters, aiming to achieve the highest level of accuracy in predicted models. The R 2 scores were recorded as 0.956 for Cr in water, 0.987 for Cr in the plant, 0.992 for bioconcentration factor (BCF), and 0.957 for Cr removal through the Firefly-RF model. The findings illustrated superior prediction performance from the random forest models when compared to the response surface methodology. The conclusion is drawn that metal-based nanoparticles (NPs) can effectively be utilized for nano-phytoremediation of heavy metals. This study has uncovered a promising outlook for the utilization of nanoparticles in nano-phytoremediation. This study is expected to pave the way for future research on the topic, facilitating further exploration of various nanoparticles and a thorough evaluation of their potential in aquatic ecosystems. Graphical Abstract

Investigating the comparative utility of ECMWF precipitation forecasts as an alternative to reanalysis data - Muhammad Amjad; M. Tugrul Yilmaz; Ismail Yucel; Koray K. Yilmaz; Kurtuluş Öztürk (Hydrological Sciences Journal, 2024)

Sugarcane/soybean intercropping enhances crop productivity, nutrient uptake, and net economic return with reduced inputs - Muhammad Ali Raza; Atta Mohi Ud Din; Hina Gul; Wang Zhiqi; Hassan Shehryar Yasin; Muhammad Hayder Bin Khalid; Nasir Iqbal; Amjad Saeed; Birra Bukhari; Munirah Abdullah Al Dosary; Chen Juan; Xue Liang; et al. (Field Crops Research, 2024)

Yeast-based solutions in controlling plant pathogens - Amjad Ali; Fatih Ölmez; Muhammad Ahmad Zeshan; Mustansar Mubeen; Yasir Iftikhar; Ashara Sajid; Muhammad Abid; Ajay Kumar; Praveen Kumar Divvela; Manoj Kumar Solanki (Biocatalysis and Agricultural Biotechnology, 2024)

Hydrologic interpretation of machine learning models for 10-daily streamflow simulation in climate sensitive upper Indus catchments - Haris Mushtaq; Taimoor Akhtar; Muhammad Zia ur Rahman Hashmi; Amjad Masood; Fahad Saeed (Theoretical and Applied Climatology, 2024)
Machine learning for hydrologic modeling has seen significant recent development and has been suggested as a valuable augmentation to physical hydrological modeling, especially in data-scarce catchments. In Pakistan, surface water flows predominantly originate from the transboundary Upper Indus sub-catchments of Chenab, Jhelum, Indus, and Kabul rivers. These catchments have large drainage areas, climate-driven streamflows, high variations in elevation, and limited streamflow gauge coverage. Hence, using machine learning models for data-driven river flow modeling may be well-suited for these catchments. However, hydrologic interpretability of machine learning models is important for the practical use of such models for these catchments. Thus, the current study besides evaluating the potential of three machine learning models (XGBOOST, Classification and Regression Trees(CART), and RandomForest) for streamflow simulation also focused on the hydrologic interpretation of machine learning models using SHapley Additive exPlananations (SHAP). All of these models performed well and the range of $$R^2$$ R 2 and Nasche-Efficiency for all three models lies between 0.61 to 0.90. Moreover, SHAP correctly identified minimum temperature as the most critical feature in glacier-fed Indus and Chenab catchments. It also provides logical insights into interactions between minimum temperature and precipitation for the indus and Chenab catchment. The findings of this study strongly illustrate the usefulness of SHAP analysis in interpreting the behavior of data-scarce high-elevation climate-sensitive catchments using tree-based machine learning models.

Heavy metal exposure and metabolomics analysis: an emerging frontier in environmental health - Kainat Ilyas; Hajra Iqbal; Muhammad Sajid Hamid Akash; Kanwal Rehman; Amjad Hussain (Environmental Science and Pollution Research, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Melatonin alleviates cadmium phytotoxicity through regulation of growth, photosynthesis, and antioxidant potential in two pepper genotypes - Muhammad Saqib; Umbreen Shahzad; Zakia Abid; Faisal Zulfiqar; Rahul Kumar Tiwari; Milan Kumar Lal; Waleed Amjad Khan; Mohamed A. El-Sheikh; Muhammad Ahsan Altaf (Acta Physiologiae Plantarum, 2024)

Geochemical and isotopic constraints on the origin and evolution of the Matum-Das tonalite and mafic enclaves from the Kohistan Batholith, Northern Pakistan - Mubasir Ali; Kui-Dong Zhao; Chao Wang; Hafiz U. Rehman; Amjad Hussain; Munazzam Ali Mahar; Muhammad Farhan; Wasiq Lutfi (Lithos, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Response surface methodology and artificial intelligence modeling for in vitro regeneration of Brazilian micro sword (Lilaeopsis brasiliensis) - Seyid Amjad Ali; Muhammad Aasim (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In this study, response surface methodology (RSM) was used to optimize in vitro regeneration of the Brazilian micro sword ( Lilaeopsis brasiliensis) aquatic plant, followed by data prediction and validation using machine learning algorithms. The basal salt, sucrose and Benzyaminopurine (BAP) concentrations were derived from Box-Behnken design of RSM. The response surface regression analysis revealed that 1.0 g/L MS + 0.1 mg/L BAP + 25 g/L sucrose was optimized for maximum regeneration (100%), shoot counts (63.2), and fresh weight (1.382 g). The RSM-based predicted scores were fairly similar to the actual scores, which were 100% regeneration, 63.39 shoot counts, and 1.44 g fresh weight. Pareto charts analysis illustrated the significance of MS for regeneration and fresh weight but remained insignificant. Conversely, MS × BAP was found to be the most crucial factor for the shoot counts, with MS coming in second and having a major influence. The analysis of the normal plot ascertained the negative impact of elevated MS concentration on shoot counts and enhanced shoot counts from the combination of MS × BAP. Results were further optimized by constructing contour and surface plots. The response optimizer tool demonstrated that maximum shoot counts of 63.26 and 1.454 g fresh weight can be taken from the combination of 1.0 g/L MS + 0.114 mg/L BAP + 23.94 g/L. Using three distinct performance criterias, the results of machine learning models showed that the multilayer perceptron (MLP) model performed better than the random forest (RF) model. Our findings suggest that the results may be utilized to optimize various input variables using RSM and verified via ML models. Key message Optimization of in vitro whole plant regeneration of Brazilian sword wood using response surface methodology Data analysis through ANOVA, response surface regression anlaysis and machine learning Graphical presentation of data via Pareto charts, normal plots, contour plots and surface plots for optimization Better performance of ANN-based MLP model compared to decision tree based RF model Graphical abstract

Artificial intelligence models for validating and predicting the impact of chemical priming of hydrogen peroxide (H2O2) and light emitting diodes on in vitro grown industrial hemp (Cannabis sativa L.) - Muhammad Aasim; Buşra Yıldırım; Ahmet Say; Seyid Amjad Ali; Selim Aytaç; Muhammad Azhar Nadeem (Plant Molecular Biology, 2024)

Biochar: Black Gold for Sustainable Agriculture and Fortification Against Plant Pathogens—A Review - Usman Arshad; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Ali; Muhammad Nadeem Shah; Muhammad Jabran; Muhammad Amjad Ali (Journal of Crop Health, 2024)

Legacy effect of long-term rice–crab co-culture on N2O emissions in paddy soils - Weijing Li; Yibin Zhang; Hongyuan Wang; Bingqian Fan; Muhammad Amjad Bashir; Ke Jin; Hongbin Liu (Applied Soil Ecology, 2024)

Smart and sustainable urban manufacturing for a circular economy - Muhammad Saad Amjad; Nancy Diaz-Elsayed (Environment, Development and Sustainability, 2024)

Silicon-nanoparticles loaded biochar for soil arsenic immobilization and alleviation of phytotoxicity in barley: Implications for human health risk - Muhammad Asif Naeem; Abrar Shabbir; Muhammad Imran; Sajjad Ahmad; Muhammad Shahid; Behzad Murtaza; Muhammad Amjad; Waqas-ud-Din Khan (Environmental Science and Pollution Research, 2024)

UV-blocking and photocatalytic properties of Ag-coated cotton fabrics with Si binders for photo-degradation of recalcitrant dyes in aqueous solutions under sunlight - Muhammad Amjad; Ayesha Mohyuddin; Wajad Ulfat; Hui Hwang Goh; Mohd Hafiz Dzarfan Othman; Tonni Agustiono Kurniawan (Journal of Environmental Management, 2024)

Investigating biodiesel production from Chicken fat oil using bi-functional catalysts and microbubble mediated mass transfer - Maryam Asif; Fahad Javed; Muhammad Younas; Mazhar Amjad Gillani; William B. Zimmerman; Fahad Rehman (Fuel, 2024)

Multifunctional role of nanoparticles for the diagnosis and therapeutics of cardiovascular diseases - Ihtesham Arshad; Ayesha Kanwal; Imran Zafar; Ahsanullah Unar; Hanane Mouada; Iashia Tur Razia; Safina Arif; Muhammad Ahsan; Mohammad Amjad Kamal; Summya Rashid; Khalid Ali Khan; Rohit Sharma (Environmental Research, 2024)

MOFs coupled transition metals, graphene, and MXenes: Emerging electrocatalysts for hydrogen evolution reaction - Abdul Hanan; Muhammad Nazim Lakhan; Faiza Bibi; Amjad Khan; Irfan Ali Soomro; Altaf Hussain; Umair Aftab (Chemical Engineering Journal, 2024)

Optimised stacked machine learning algorithms for genomics and genetics disorder detection in the healthcare industry - Amjad Rehman; Muhammad Mujahid; Tanzila Saba; Gwanggil Jeon (Functional & Integrative Genomics, 2024)

Chitosan nanoparticles encapsulating curcumin counteract salt-mediated ionic toxicity in wheat seedlings: an ecofriendly and sustainable approach - Arruje Hameed; Waqas Maqsood; Amjad Hameed; Muhammad Abdul Qayyum; Toheed Ahmed; Tahir Farooq (Environmental Science and Pollution Research, 2024)

Contribution to the pollen morphology of Astragalus L. section Aegacantha Bunge (Galegeae-Fabaceae) and its systematic significance - Amjad Khan; Mushtaq Ahmad; Amir Sultan; Zakir Ullah; Khawar Majeed; Tariq Ullah; Muhammad Zafar (Palynology, 2024)

Copolymerization of ethylene and isoprene via silicon bridge metallocene [rac-Me2Si(2-Me-4-Ph-Ind)2ZrCl2] catalyst: A new way to control the composition and microstructure of copolymers - Amjad Ali; Ahmad Naveed; Anna Maroń; Muhammad Adnan Younis; Jamile Mohammadi Moradian; Balal Yousaf; Tariq Aziz; Rai Nauman Ali; Naushad Ahmad; Suliman Yousef Alomar; Fan Zheqiang; Li Guo (Chemosphere, 2024)

Protein extracted from Moringa oleifera Lam. Leaves: Bio-evaluation and characterization as suitable plant-based meat-protein alternative - Muhammad Sameem Javed; Smara Qaiser Alvi; Adnan Amjad; Hasan Sardar; Muhammad Junaid Anwar; Asma Javid; Sami Abou Fayssal; Pankaj Kumar; Tracy Abou Fayssal; Saikh M. Wabaidur; Mohammad K. Okla; Ibrahim A. Saleh; et al. (Regulatory Toxicology and Pharmacology, 2024)

Circular economy-based integrated farming system for indigenous chicken: Fostering food security and sustainability - Iffat Abbas Abbasi; Amjad Shamim; Muhammad Kashif Shad; Hasbullah Ashari; Ijaz Yusuf (Journal of Cleaner Production, 2024)

RETRACTED: Alleviation of microplastic toxicity in soybean by arbuscular mycorrhizal fungi: Regulating glyoxalase system and root nodule organic acid - Zeeshan Khan; Tariq Shah; Muhammad Asad; Khadija Amjad; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Genome-wide association studies revealed DArTseq loci associated with agronomic traits in Turkish faba bean germplasm - Tolga Karaköy; Faruk Toklu; Eylem Tuğay Karagöl; Damla Uncuer; Yeter Çilesiz; Amjad Ali; Muhammad Azhar Nadeem; Hakan Özkan (Genetic Resources and Crop Evolution, 2024)

Genome-wide identification and characterization of wall-associated kinases, molecular docking and polysaccharide elicitation of monoterpenoid indole alkaloids in micro-propagated Catharanthus roseus - Jawad Ahmed; Yasar Sajjad; Aasia Latif; Mohammad Saeed Lodhi; Muhammad Huzafa; Chen Situ; Raza Ahmad; Muhammad Maroof Shah; Amjad Hassan (Journal of Plant Research, 2024)

An explainable two-stage machine learning approach for precipitation forecast - Ali Ulvi Galip Senocak; M. Tugrul Yilmaz; Sinan Kalkan; Ismail Yucel; Muhammad Amjad (Journal of Hydrology, 2023)

Does the impact of financial development reinforce sustainability ecological footprint? Fresh evidence from middle and high-income economies - Bilal Aslam; Guitao Zhang; Muhammad Asif Amjad; Shujun Guo; Maowang Ji (Journal of Cleaner Production, 2023)

Fabrication, characterization, and application of light weight thermal insulation material from combined buffing dust and plaster of paris for construction industry - Wajad Ulfat; Ayesha Mohyuddin; Muhammad Amjad; Mohd Hafiz Dzarfan Othman; Petros Gikas; Tonni Agustiono Kurniawan (Journal of Environmental Management, 2023)

Retention of methyl iodide on metal and TEDA impregnated activated carbon using indigenously developed setup - Talhat Yaqoob; Masroor Ahmad; Yasir Faiz; Farman Ali; Amjad Farooq; Faisal Faiz; Attaullah Shah; Muhammad Asim Irshad; Naseem Irfan; Nisar Ali; Sahid Mehmood (Environmental Research, 2023)

Sembar Formation as an Unconventional Prospect: New Insights in Evaluating Shale Gas Potential Combined with Deep Learning - Muhammad Raiees Amjad; Urooj Shakir; Muyyassar Hussain; Awais Rasul; Saqib Mehmood; Muhsan Ehsan (Natural Resources Research, 2023)

Silver hybridized polymer nanocomposite for efficient encapsulation of toxic dye from aqueous solution - Muhammad Amjad; Ayesha Mohyuddin; Wajad Ulfat; Saeed Ahmed; Abrar Ul Hassan (Nanotechnology for Environmental Engineering, 2023)

Sequence variants in different genes underlying Bardet-Biedl syndrome in four consanguineous families - Amjad Ali; Abdullah; Muhammad Bilal; Emily Kathryn Mis; Saquib Ali Lakhani; Wasim Ahmad; Imran Ullah (Molecular Biology Reports, 2023)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

Chromium removal from aqueous solution using bimetallic Bi0/Cu0-based nanocomposite biochar - Behzad Murtaza; Aqsa Naseer; Muhammad Imran; Noor S. Shah; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Muhammad Shahid; Jibran Iqbal; Ghulam Abbas; Natasha Natasha; Muhammad Amjad (Environmental Geochemistry and Health, 2023)

Exploring the moderating effect of globalization, financial development and environmental degradation nexus: a roadmap to sustainable development - Tayyaba Rani; Muhammad Asif Amjad; Nabila Asghar; Hafeez Ur Rehman (Environment, Development and Sustainability, 2023)

Policies and regulations for solar photovoltaic end-of-life waste management: Insights from China and the USA - Amjad Ali; Sheraz Alam Malik; Md Shafiullah; Muhammad Zeeshan Malik; Md Hasan Zahir (Chemosphere, 2023)

Unraveling the synergy of interface engineering α-MnO2/Bi2WO6 heterostructures and defective active sites for superdurable photocatalysis: Mechanistic insights into charge separation/transfer - Muhammad Arif; Ayaz Mahsud; Amjad Ali; Shipeng Liao; Jiawei Xia; Hai Xiao; Mohammad Azam; Tahir Muhmood; Zhansheng Lu; Yinjuan Chen (Chemical Engineering Journal, 2023)

Co-occurrence of mycotoxins and other fungal metabolites in total mixed rations of cows from dairy farms in Punjab, Pakistan - Felipe Penagos-Tabares; Mubarik Mahmood; Muhammad Zafar Ullah Khan; Hafiz Muhammad Amjad Talha; Muhammad Sajid; Kanwal Rafique; Saima Naveed; Johannes Faas; Juan Ignacio Artavia; Michael Sulyok; Anneliese Müller; Rudolf Krska; et al. (Mycotoxin Research, 2023)
After India and the USA, Pakistan is the third country leading in global dairy production, a sector of very high socioeconomic relevance in Asia. Mycotoxins can affect animal health, reproduction and productivity. This study analysed a broad range of co-occurring mycotoxins and fungal secondary metabolites derived from Alternaria , Aspergillus , Fusarium , Penicillium and other fungal species. To complete this, a validated multi-metabolite liquid chromatography/electrospray ionization-tandem mass spectrometric (LC/ESI–MS/MS) method was employed, detecting 96 of > 500 tested secondary fungal metabolites. This first preliminary study demonstrated that total mixed rations (TMRs) ( n = 30) from big commercial dairy cattle farms (> 200 lactating cows) in Punjab, Pakistan, presented ubiquitous contamination with mixtures of mycotoxins. The mean of mycotoxins per sample was 14, ranging from 11 to 20 mycotoxins among all TMR samples. Metabolites derived from other fungi and Fusarium spp. showed the highest levels, frequency and diversity among the detected fungal compounds. Among the most prevalent mycotoxins were Fusarium toxins like fumonisins B1 (FB1) (93%), B2 (FB2) (100%) and B3 (FB3) (77%) and others. Aflatoxin B1 (AFB1) was evidenced in 40% of the samples, and 7% exceeded the EU maximum limit for feeding dairy cattle (5 µg/kg at 88% dry matter). No other mycotoxin exceeds the EU guidance values (GVs). Additionally, we found that dietary ingredients like corn grain, soybean meal and canola meal were related to increased contamination of some mycotoxins (like FB1, FB2 and FB3) in TMR from the province of Punjab, Pakistan. Among typical forage sources, the content of maize silage was ubiquitous. Individually, the detected mycotoxins represented relatively low levels. However, under a realistic scenario, long-term exposure to multiple mycotoxins and other fungal secondary metabolites can exert unpredictable effects on animal health, reproduction and productivity. Except for ergot alkaloids (73%), all the groups of metabolites (i.e. derived from Alternaria spp., Aspergillus spp., Fusarium spp., Penicillium spp. and other fungi) occurred in 100% of the TMR samples. At individual levels, no other mycotoxins than AFB1 represented a considerable risk; however, the high levels of co-occurrence with several mycotoxins/metabolites suggest that long-term exposure should be considered because of their potential toxicological interactions (additive or synergistic effects).

Ab initio insight into the physical properties of MgXH3 (X = Co, Cu, Ni) lead-free perovskite for hydrogen storage application - Zia ur Rehman; Muhammad Awais Rehman; Bushra Rehman; Surajudeen Sikiru; Saima Qureshi; Esraa Mousa Ali; Muhammad Awais; Mahnoor Amjad; Iqra Iqbal; Anam Rafique; Saira Bibi (Environmental Science and Pollution Research, 2023)

Effect of green synthesized cerium oxide nanoparticles on fungal disease of wheat plants: A field study - Modhi O. Alotaibi; Nahaa M. Alotaibi; Adel M. Ghoneim; Noor ul Ain; Muhammad Atif Irshad; Rab Nawaz; Tahir Abbas; Amjad Abbas; Muhammad Rizwan; Shafaqat Ali (Chemosphere, 2023)

Nanosheet arrays of iron oxide for enhanced ammonia synthesis via electrochemical nitrogen reduction for prospective algal membrane bioreactors - Muhammad Adnan Younis; Saira Manzoor; Amjad Ali; Fazal Haq; Tariq Aziz; Mehwish Kiran; Arshad Farid; Mohamed E. El Sayed; Mohammad N. Murshed; Zeinhom M. El-Bahy; Muhammad Saeed Akhtar (Chemosphere, 2023)

Fate of 15N-labelled urea as affected by long-term manure substitution - Fuyue Dai; Bingqian Fan; Jungai Li; Yitao Zhang; Hongyuan Wang; Zhen Wang; Muhammad Amjad Bashir; Golnaz Ezzati; Limei Zhai; Hong J. Di; Hongbin Liu (Science of The Total Environment, 2023)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

A systematic review of physiological signals based driver drowsiness detection systems - Adil Ali Saleem; Hafeez Ur Rehman Siddiqui; Muhammad Amjad Raza; Furqan Rustam; Sandra Dudley; Imran Ashraf (Cognitive Neurodynamics, 2023)

Artificial neural network and decision tree–based models for prediction and validation of in vitro organogenesis of two hydrophytes—Hemianthus callitrichoides and Riccia fluitans - Esra Özcan; Hasan Hüseyin Atar; Seyid Amjad Ali; Muhammad Aasim (In Vitro Cellular & Developmental Biology - Plant, 2023)

Adsorptive and photocatalytic degradation potential of porous polymeric materials for removal of pesticides, pharmaceuticals, and dyes-based emerging contaminants from water - Azeem Intisar; Arooj Ramzan; Shahzar Hafeez; Nazim Hussain; Muhammad Irfan; Nasir Shakeel; Komal Aziz Gill; Amjad Iqbal; Marcin Janczarek; Teofil Jesionowski (Chemosphere, 2023)

RETRACTED: Strigolactone decreases cadmium concentrations by regulating cadmium localization and glyoxalase defense system: Effects on nodules organic acids and soybean yield - Tariq Shah; Muhammad Asad; Zeeshan Khan; Khadija Amjad; Abdulaziz Abdullah Alsahli; Roberto D'amato (Chemosphere, 2023)

Rhizosphere effect on the relationship between dissolved organic matter and functional genes in contaminated soil - Qingqing Wang; Shiyang Wei; Yang Zhou; Ondřej Mašek; Muhammad Amjad Khan; Dong Li; Quan Liu; Yin Liu; Wenkang Lu; Xuesong Su; Zhiqiang Zhu; Xiaojun Zhao; et al. (Journal of Environmental Management, 2023)

Photocatalytic and Antibacterial Potential of Chitosan Supported Nickel Oxide/Zinc Oxide Composite Synthesized by Alcohothermal Method - Amna Yasin; Tousif Hussain; Riaz Ahmad; Urooj Shuaib; Muhammad Amjad; Sajjad Ahmad; M. Imranullah (Water, Air, & Soil Pollution, 2023)

Different behaviors in nitrogen leaching between soil types following the substitution of synthetic fertilizers by manure - Xinzhong Du; Yitao Zhang; Jungai Li; Chang Peng; Hongyuan Wang; Muhammad Amjad Bashir; Zhen Wang; Limei Zhai; Hong J. Di; Hongbin Liu (Nutrient Cycling in Agroecosystems, 2023)

Global digital divide and environmental degradation in Africa - Sana Sarwar; Muhammad Rizwan Yaseen; Muhammad Sohail Amjad Makhdum; Azeem Sardar; Nazia Yasmeen; Rameen Shahid (Environmental Science and Pollution Research, 2023)

Moderating the role of social progress with greenhouse gases to determine the health vulnerability in developing countries - Muhammad Asif Amjad (Environmental Science and Pollution Research, 2023)

Pathway analysis of food security by employing climate change, water, and agriculture nexus in Pakistan: partial least square structural equation modeling - Muhammad Usman; Asghar Ali; Muhammad Khalid Bashir; Khalid Mushtaq; Abdul Ghafoor; Fiza Amjad; Muhammad Hashim; Sajjad Ahmad Baig (Environmental Science and Pollution Research, 2023)

Novel concept for water scarcity quantification considering nonconventional and virtual water resources in arid countries: Application in Gulf Cooperation Council countries - Muhammad Al Rashed; Ahmed Sefelnasr; Mohsen Sherif; Ahmed Murad; Dalal Alshamsi; Amjad Aliewi; Abdel Azim Ebraheem (Science of The Total Environment, 2023)

Soil organic carbon sequestration and modeling under conservation tillage and cropping systems in a rainfed agriculture - Sana ur Rehman; Shahzada Sohail Ijaz; Muhammad Ali Raza; Atta Mohi Ud Din; Khalid Saifullah Khan; Shroz Fatima; Taqi Raza; Sajid Mehmood; Amjad Saeed; Muhammad Ansar (European Journal of Agronomy, 2023)

Correction to: The impact of geopolitical risk, governance, technological innovations, energy use, and foreign direct investment on CO2 emissions in the BRICS region - Ijaz Uddin; Muhammad Usman; Najia Saqib; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2023)

Petiole micromorphology in Brassicaceous taxa and its potential for accurate taxonomic identification - Wajia Noor; Muhammad Zafar; Mushtaq Ahmad; Ashwaq T. Althobaiti; Mohamed Fawzy Ramadan; Trobjon Makhkamov; Yusufjon Gafforov; Akramjon Yuldashev; Oybek Mamarakhimov; Omer Kilic; Heba F. Eid; Talip Şahin; et al. (Flora, 2023)

Biochars Affect the Mobility of Carcinogenic Polycyclic Aromatic Hydrocarbons (PAHs) in Amended Soil and Their Bioaccumulation in Spinach - Muhammad Waqas; Sardar Khan; Cai Chao; Jawed Nawab; Isha Shamshad; Shah Jehan; Iqbal Haider; Ihsan Ullah; Muhammad Amjad Khan (Water, Air, & Soil Pollution, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Machine Learning and Artificial Neural Networks-Based Approach to Model and Optimize Ethyl Methanesulfonate and Sodium Azide Induced In Vitro Regeneration and Morphogenic Traits of Water Hyssops (Bacopa monnieri L.) - Kubra Mirza; Muhammad Aasim; Ramzan Katırcı; Mehmet Karataş; Seyid Amjad Ali (Journal of Plant Growth Regulation, 2023)

The impact of geopolitical risk, governance, technological innovations, energy use, and foreign direct investment on CO2 emissions in the BRICS region - Ijaz Uddin; Muhammad Usman; Najia Saqib; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2023)

Performance evaluation of Standardized Copula‐based Drought Index with Reconnaissance Drought Index and Standardized Precipitation Temperature Index using severity–duration frequency curves over Balochistan, Pakistan - Hamd Ullah; Muhammad Akbar; Firdos Khan; Muhammad Amjad (International Journal of Climatology, 2023)
Drought and aridity are good measures to study climate change that are measured using several indices. In this study, the performance of Standardized Copula‐based Drought Index (SCDI) is compared with Standardized Precipitation Temperature Index (SPTI) and Reconnaissance Drought Index (RDI) for measuring drought in Balochistan province of Pakistan. These standardized drought indices combine the outcomes of De‐Martone Aridity Index (DAI) and UNEP Aridity Index (UAI). SCDI is calculated using probability distributions and copula models that combine the outcomes of UAI and DAI utilizing data of precipitation, potential evapotranspiration (PE), and temperature. Climate data from nine including arid and humid metrological stations are used to study drought conditions in Balochistan province. SCDI outcomes are graphically and numerically compared with SPTI and RDI. Selected drought indices are compared based on frequency of drought and wet events occurred in moderate, severe, and extreme drought categories, which indicate that SCDI has maximum number of events in these categories. It gives better results due to the utilization of more climate data as compared to RDI and SPTI. Severity–duration frequency curves are used to find future projections which shows that drought severity and drought duration have increasing trend with the passage of time. The indices have more differences in results of arid stations. The results indicate that there are no significant chances of drought at lower time scales, but the chances increase with the increase in time scale. The SCDI may also be more useful for agricultural and hydrological droughts due to temperature and PE variables. This study's results will be helpful for climate planning in Balochistan province.

Effects of prepartum melatonin treatment and suckling on postpartum reproductive performance of Beetal goats under subtropical conditions - Muhammad Afzaal; Muhammad Irfan-ur-Rehman Khan; Waqas Ahmad; Amir Hayat; Qasir Abbas; Muhammad Arshad; Nasir Hameed; Imran Mohsin; Amjad Riaz (Small Ruminant Research, 2023)

Precise geopressure predictions in active foreland basins: An application of deep feedforward neural networks - Muhammad Raiees Amjad; Muhammad Zafar; Muhammad Bilal Malik; Zohaib Naseer (Journal of Asian Earth Sciences, 2023)

Production of fuel oil from elastomer rubber waste via methanothermal liquefaction - Nabeel Ahmad; Nauman Ahmad; Usama Ahmed; Abdul Gani Abdul Jameel; Um-e-Salma Amjad; Murid Hussain; Muhammad Maaz Arif (Fuel, 2023)

Role of silica-based porous cellulose nanocrystals in improving water absorption and mechanical properties - Tariq Aziz; Arshad Farid; Fazal Haq; Mehwish Kiran; Naveed Ullah; Shah Faisal; Amjad Ali; Farman Ullah Khan; Siming You; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; et al. (Environmental Research, 2023)

Moringa oleifera leaf extract mediated green synthesis of silver nanoparticles and their antibacterial effect against selected gram-negative strains - Mehwish Younas; Muhammad Hidayat Rasool; Mohsin Khurshid; Amjad Khan; Muhammad Zeshan Nawaz; Ijaz Ahmad; Muhammad Nazim Lakhan (Biochemical Systematics and Ecology, 2023)

Estimation of genetic divergence in wheat genotypes based on agro-morphological traits through agglomerative hierarchical clustering and principal component analysis - Anam Khalid; Amjad Hameed; Muhammad Farrukh Tahir (Cereal Research Communications, 2023)

Human Health and Ecological Risks Associated with Total and Bioaccessible Concentrations of Cadmium and Lead in Urban Park Soils - Muhammad Amjad Khan; Javed Nawab; Anwarzeb Khan; Mark L. Brusseau; Shah Nawaz Khan; Neelum Ali; Saraj Bahadur; Sardar Khan; Qing Huang (Bulletin of Environmental Contamination and Toxicology, 2023)

Task-specific polymeric membranes to achieve high gas-liquid mass transfer - Muhammad Tayyab Khalid; Tanzila Anjum; Asim Laeeq Khan; Fahad Rehman; Muhammad Aslam; Mazhar Amjad Gilani; Faheem Hassan Akhtar; Mungyu Lee; In Seop Chang; Muhammad Yasin (Chemosphere, 2023)

Separation and purification of syngas-derived hydrogen: A comparative evaluation of membrane- and cryogenic-assisted approaches - Ahmad Naquash; Muhammad Abdul Qyyum; Yus Donald Chaniago; Amjad Riaz; Fatma Yehia; Hankwon Lim; Moonyong Lee (Chemosphere, 2023)

Abundance, spatial distribution, and characteristics of microplastics in agricultural soils and their relationship with contributing factors - Muhammad Amjad Khan; Qing Huang; Sardar Khan; Qingqing Wang; Jingjing Huang; Shah Fahad; Muhammad Sajjad; Yin Liu; Ondřej Mašek; Xiaohui Li; Junfeng Wang; Xiaomao Song (Journal of Environmental Management, 2023)

Artificial neural network modeling for deciphering the in vitro induced salt stress tolerance in chickpea (Cicer arietinum L) - Muhammad Aasim; Fatma Akin; Seyid Amjad Ali; Mehmet Burak Taskin; Muslume Sevba Colak; Khalid Mahmood Khawar (Physiology and Molecular Biology of Plants, 2023)

Opportunities and constraints for cleaner production policy in the developing world: a case study of Sindh Region, Pakistan - Love Kumar; Sohail Ali Naqvi; Matthew J. Deitch; Muhammad Jibran Khalid; Komal Naeem; Arjmand Qayyum Amjad; Avinash Kumar; Tesfay Gebretsadkan Gebremicael; Masood Arshad (Environment, Development and Sustainability, 2023)

Artificial intelligence–based approaches to evaluate and optimize phytoremediation potential of in vitro regenerated aquatic macrophyte Ceratophyllum demersum L. - Muhammad Aasim; Seyid Amjad Ali; Senar Aydin; Allah Bakhsh; Canan Sogukpinar; Mehmet Karatas; Khalid Mahmood Khawar; Mehmet Emin Aydin (Environmental Science and Pollution Research, 2023)

Porous Ag3VO4/KIT-6 composite: Synthesis, characterization and enhanced photocatalytic performance for degradation of Congo Red - Iqra Mahboob; Iqrash Shafiq; Sumeer Shafique; Parveen Akhter; Mamoona Munir; Muhammad Saeed; Muhammad Shahid Nazir; Um-e-Salma Amjad; Farrukh Jamil; Nabeel Ahmad; Young-Kwon Park; Murid Hussain (Chemosphere, 2023)

Cow bone-derived biochar enhances microbial biomass and alters bacterial community composition and diversity in a smelter contaminated soil - Muhammad Azeem; Parimala Gnana Soundari Arockiam Jeyasundar; Amjad Ali; Luqman Riaz; Khalid S. Khan; Qaiser Hussain; Hafiz A. Kareem; Fakhar Abbas; Abdul Latif; Ali Majrashi; Esmat F. Ali; Ronghua Li; et al. (Environmental Research, 2023)

The role of MnO2 crystal facets in aluminothermic reaction of MnO2/nAl composite - Muhammad Amjad Majeed; Jianyong Xu; Wenchao Zhang; Xiwen Wang; Jiaxin Wang; Junhong Chen; Gexing Yang; Qi Liu; Bonan Gu (Chemical Engineering Journal, 2023)

Nickel toxicity pretreatment attenuates salt stress by activating antioxidative system and ion homeostasis in tomato (Solanum lycopersicon L.): an interplay from mild to severe stress - Muhammad Azeem Subhani; Muhammad Amjad; Muhammad Mohsin Iqbal; Behzad Murtaza; Muhammad Imran; Muhammad Asif Naeem; Ghulam Abbas; Mathias Neumann Andersen (Environmental Geochemistry and Health, 2023)

Do financial development, economic growth, energy consumption, and trade openness contribute to increase carbon emission in Pakistan? An insight based on ARDL bound testing approach - Muhammad Usman; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum; Muhammad Rizwan Yaseen; Abdul Majeed Nadeem (Environment, Development and Sustainability, 2023)

The influence of compost amendments on bioaccumulation of potentially toxic elements by pea plant cultivated in mine degraded soils - Abdulnour Ali Jazem Ghanim; Muhammad Azhar Shah; Mehboob Alam; Anwarzeb Khan; Muhammad Amjad Khan; Saifur Rahman; Mabkhoot A. Alsaiari; Mohammed Jalalah; Mohammad Kamal Asif Khan; Muhammad Irfan; Zawar Hussain (Arabian Journal of Geosciences, 2023)

Identification and primary distribution of Citrus viroid V in citrus in Punjab, Pakistan - Amjad Ali; Ummad ud din Umar; Sohail Akhtar; Muhammad Taimoor Shakeel; Ateeq ur Rehman; Muhammad Nouman Tahir; Sagheer Atta; Mahmoud Moustafa; Fatih Ölmez; Rashida Parveen (Molecular Biology Reports, 2022)

Leaf Area Regulates the Growth Rates and Seed Yield of Soybean (Glycine max L. Merr.) in Intercropping System - Muhammad Ali Raza; Hina Gul; Ali Hasnain; Muhammad Hayder Bin Khalid; Sajad Hussain; Ghulam Abbas; Waqas Ahmed; Muhammad Jawad Babar; Zaheer Ahmed; Amjad Saeed; Muhammad Umair Riaz; Azeem Iqbal Khan; et al. (International Journal of Plant Production, 2022)

Analyzing the impact of access to electricity and biomass energy consumption on infant mortality rate: a global perspective - Nabila Asghar; Muhammad Asif Amjad; Hafeez ur Rehman (Environmental Science and Pollution Research, 2022)

Combined application of poultry litter biochar with NPK fertilizer mitigates the effects of stress in wheat (Triticum aestivum L.) grown on chromium contaminated soil - Irfana Lalarukh; Sami A. Al-Dhumri; Laith Khalil Tawfeeq Al-Ani; Muhammad Shahbaz; Syeda Fasiha Amjad; Nida Mansoora; Wasimah B. Al-Shammari; Fatimah S. Alhusayni; Mohammad M. Almutari (Plant and Soil, 2022)

Synthesis, theoretical investigations and biological evaluation of ibuprofen drug hybrids - Adina Tatheer; Shahzad Murtaza; Naghmana Kausar; Ataf Ali Altaf; Samia Kausar; Safeer Ahmed; Shabbir Muhammad; Amjad Hussain (Medicinal Chemistry Research, 2022)

Revisiting the environmental impact of financial development on economic growth and carbon emissions: evidence from South Asian economies - Tayyaba Rani; Muhammad Asif Amjad; Nabila Asghar; Hafeez Ur Rehman (Clean Technologies and Environmental Policy, 2022)

Coupling biochar with microbial inoculants improves maize growth and nutrients acquisition under phosphorous-limited soil - Hafiz Muhammad Rashad Javeed; Rimsha Naeem; Mazhar Ali; Rafi Qamar; Muhammad Aqeel Sarwar; Fahim Nawaz; Atique-ur-Rehman; Muhammad Shehzad; Amjad Farooq; Haseeb-ur-Rehman; Samina Khalid; Khuram Mubeen; et al. (Acta Physiologiae Plantarum, 2022)

Effectiveness of various polysaccharides for controlling properties of alkali-activated manganese-rich slag pastes - Shehzad Mussawar; Muhammad Ali Sikandar; Zafar Baloch; Amjad Naseer; Syed Azmat Ali Shah (European Journal of Environmental and Civil Engineering, 2022)

Optimization of Process Parameters in Friction Stir Welding of Aluminum 5451 in Marine Applications - Shoaib Ahmed; Rana Atta ur Rahman; Awais Awan; Sajjad Ahmad; Waseem Akram; Muhammad Amjad; Mohd Yazid Yahya; Seyed Saeid Rahimian Koloor (Journal of Marine Science and Engineering, 2022)
Friction stir welding (FSW) is one of the primary fabrication techniques for joining different components, and it has become popular, especially in aluminum alloy structures for marine applications. The welded joint with the friction stir process greatly depends on the process parameters, i.e., feed rate, rotational speed, and pin profile of the tool. In the current study, plates of aluminum 5451 alloy were joined by the FSW technique, and the Taguchi method was used to find the process parameters at an optimal level. The maximum value of tensile strength, i.e., 160.6907 MPa, was achieved using optimum welding conditions of a tool rotation speed of 1400, a feed rate of 18 mm/min, and the tool pin with threads. The maximum value of hardness, i.e., 81.056 HV, was achieved using optimum conditions of 1200 tool rotational speed and a feed rate of 18 mm/min with a tool pin profile having threads. In addition, the contribution in terms of the percentage of each input parameter was found by the analysis of variance (ANOVA). The ANOVA results revealed that the pin profile of the tool has the maximum contribution of 67.77% and 62.42% in achieving the optimum value of tensile strength and hardness, respectively. The study also investigated the joint efficiency of the friction stir welded joint, hardness at the weld zone, and metallography on FSW samples at the optimized level. The effectiveness and reliability of FSW joints for shipping industry applications can be observed by joint efficiency. That was investigated at optimum conditions, and it comes out to be 80.5%.

Bioaccumulation and Health Risk Assessment of Heavy Metal (loid)s in Different Fish Species of Hainan Island, China - Tauseef Ahmad; Sumaira Gul; Muhammad Amjad Khan; Xiaoping Diao; Ashfaq Ahmad; Shakil Ahmad (Thalassas: An International Journal of Marine Sciences, 2022)

Light-emitting diodes induced in vitro regeneration of Alternanthera reineckii mini and validation via machine learning algorithms - Muhammad Aasim; Seyid Amjad Ali; Pınar Bekiş; Muhammad Azhar Nadeem (In Vitro Cellular & Developmental Biology - Plant, 2022)

Human health risk surveillance of polychlorinated biphenyls in bovine milk from alluvial plain of Punjab, Pakistan - Saman Sana; Abdul Qadir; Neil P. Evans; Mehvish Mumtaz; Ambreena Javaid; Amjad Khan; Saif-ur-Rehman Kashif; Habib ur Rehman; Muhammad Zafar Hashmi (Environmental Science and Pollution Research, 2022)

Enhancement of chromate phytoremediation and soil reclamation potential of Brassica campestris L. by Aspergillus niger - Muhammad Qadir; Anwar Hussain; Mohib Shah; Muhammad Hamayun; Amjad Iqbal; Nadia (Environmental Science and Pollution Research, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Nexus between fossil fuel consumption and infant mortality rate: a non-linear analysis - Maqbool Hussain Sial; Noman Arshed; Muhammad Asif Amjad; Yousaf Ali Khan (Environmental Science and Pollution Research, 2022)

Occurrence of Microplastics and Heavy Metals in Aquatic and Agroecosystem: A Case Study - Tanveer Ahmad; Muhammad Amjad; Qumer Iqbal; Asmat Batool; Anam Noor; Muhammad Jafir; Hammad Hussain; Muhammad Irfan (Bulletin of Environmental Contamination and Toxicology, 2022)

Development of Optimized Sumatriptan–Prochlorperazine Combined Orodispersible Films Without Disintegrant: in vitro, ex vivo and in vivo Characterization - Sana Javed; Amjad Hussain; Pervaiz Akhtar Shah; Syed Atif Raza; Ubaid Ullah Anwer; Rahat Shamim; Fatima Rasool; Muhammad Ahsan Hafiz; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2022)

Assessment of land use/land cover changes and its effect on land surface temperature using remote sensing techniques in Southern Punjab, Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Hamid Majeed; Saeed Ahmad Qaisrani; Hafiz Mohkum Hammad; Muhammad Amjad; Iftikhar Ahmad; Shah Fahad; Naveed Ahmad; Wajid Nasim (Environmental Science and Pollution Research, 2022)

Prevalence, transmission and molecular characterization of Cotton leaf curl Multan virus infecting hollyhock plants in Pakistan - Hajra Azeem; Rashida Perveen; Muhammad Nouman Tahir; Ummad-ud-din Umar; Fatih Ölmez; Amjad Ali (Molecular Biology Reports, 2022)

Clean and sustainable transportation through electric vehicles — a user survey of three-wheeler vehicles in Pakistan - Mohammad Aamir Khan; Syed Fawad Bokhari; Aazir Khan; Muhammad Saad Amjad; Arooj Mobasher Butt; Muhammad Zeeshan Rafique (Environmental Science and Pollution Research, 2022)

Porostereum spadiceum-AGH786 Regulates the Growth and Metabolites Production in Triticum aestivum L. Under Salt Stress - Syeda Leeda Gul; Yong-Sun Moon; Muhammad Hamayun; Sumera Afzal Khan; Amjad Iqbal; Muhammad Aaqil Khan; Anwar Hussain; Maryam Shafique; Yoon-Ha Kim; Sajid Ali (Current Microbiology, 2022)

Assessment of cadmium and lead tolerance potential of quinoa (Chenopodium quinoa Willd) and its implications for phytoremediation and human health - Muhammad Amjad; Muhammad Mohsin Iqbal; Ghulam Abbas; Abu Bakar Umer Farooq; Muhammad Asif Naeem; Muhammad Imran; Behzad Murtaza; Muhammad Nadeem; Sven-Erik Jacobsen (Environmental Geochemistry and Health, 2022)

Hardwood modified and unmodified biochar amendments used for saline alkali soil remediation: phosphorus availability and its plant uptake - Ihsan Ullah; Sardar Khan; Javed Nawab; Muhammad Amjad Khan; Shah Jehan (Arabian Journal of Geosciences, 2022)

The potential role of dietary plant ingredients against mammary cancer: a comprehensive review - Amjad Hussain; Marie-Lise Bourguet-Kondracki; Farhad Hussain; Abdur Rauf; Muhammad Ibrahim; Muhammad Khalid; Hidayat Hussain; Javid Hussain; Iftikhar Ali; Anees Ahmed Khalil; Fahad A. Alhumaydhi; Muhammad Khan; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Role of sugarcane industrial byproducts on soil physicochemical properties and metal accumulation in rice - Qurat-Ul-Ain Raza; Muhammad Amjad Bashir; Abdur Rehim; Hafiz Muhammad Ali Raza (Environmental Science and Pollution Research, 2022)

Antimicrobial Resistance of Shigella flexneri in Pakistani Pediatric Population Reveals an Increased Trend of Third-Generation Cephalosporin Resistance - Iqbal Nisa; Mohammad Haroon; Arnold Driessen; Jeroen Nijland; Hazir Rahman; Nusrat Yasin; Mubashir Hussain; Taj Ali Khan; Amjad Ali; Saeed Ahmad Khan; Muhammad Qasim (Current Microbiology, 2022)

Heavy metal tolerant endophytic fungi Aspergillus welwitschiae improves growth, ceasing metal uptake and strengthening antioxidant system in Glycine max L. - Husna; Anwar Hussain; Mohib Shah; Muhammad Hamayun; Muhammad Qadir; Amjad Iqbal (Environmental Science and Pollution Research, 2022)

Multivariate analysis of accumulation and critical risk analysis of potentially hazardous elements in forage crops - Muhammad Usman; Behzad Murtaza; Natasha Natasha; Muhammad Imran; Ghulam Abbas; Muhammad Amjad; Muhammad Shahid; Sobhy M. Ibrahim; Gary Owens; Ghulam Murtaza (Environmental Monitoring and Assessment, 2022)

Salinity modulates lead (Pb) tolerance and phytoremediation potential of quinoa: a multivariate comparison of physiological and biochemical attributes - Azka Iftikhar; Ghulam Abbas; Muhammad Saqib; Arslan Shabbir; Muhammad Amjad; Muhammad Shahid; Iftikhar Ahmad; Shahid Iqbal; Saeed Ahmad Qaisrani (Environmental Geochemistry and Health, 2022)

Heavy metal bioavailability in the earthworm-assisted soils of different land types of Pakistan - Fouzia Bakht; Sardar Khan; Said Muhammad; Muhammad Amjad Khan (Arabian Journal of Geosciences, 2022)

Quest for Novel Preventive and Therapeutic Options Against Multidrug-Resistant Pseudomonas aeruginosa - Sidra Irum; Saadia Andleeb; Amjad Ali; Muhammad Ibrahim Rashid; Mahnoor Majid (International Journal of Peptide Research and Therapeutics, 2021)

Pseudocitrobacter anthropi reduces heavy metal uptake and improves phytohormones and antioxidant system in Glycine max L. - Husna; Anwar Hussain; Mohib Shah; Muhammad Hamayun; Amjad Iqbal; Waheed Murad; Muhammad Irshad; Muhammad Qadir; Ho-Youn Kim (World Journal of Microbiology and Biotechnology, 2021)

Impregnation on activated carbon for removal of chemical warfare agents (CWAs) and radioactive content - Sidra Shaoor Kiani; Amjad Farooq; Masroor Ahmad; Naseem Irfan; Mohsan Nawaz; Muhammad Asim Irshad (Environmental Science and Pollution Research, 2021)

Modeling financial development, tourism, energy consumption, and environmental quality: Is there any discrepancy between developing and developed countries? - Muhammad Usman; Muhammad Rizwan Yaseen; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2021)

Next-generation sequencing studies on the E1-HVR1 region of hepatitis C virus (HCV) from non-high-risk HCV patients living in Punjab and Khyber Pakhtunkhwa, Pakistan - Javeria Rafique Rao; Shazia Rafique; Amjad Ali; Gouhar Rehman; Muhammad Ilyas; Muhammad Idrees (Archives of Virology, 2021)

Preparation and Characterization of pH-Independent Sustained-Release Tablets Containing Hot Melt Extruded Solid Dispersions of Clarithromycin - Qazi Amir Ijaz; Sumera Latif; Qurat-ul-ain Shoaib; Memoona Rashid; Muhammad Sohail Arshad; Amjad Hussain; Nadeem Irfan Bukhari; Sohail Riaz; Nasir Abbas (AAPS PharmSciTech, 2021)

Antioxidative and Anti-inflammatory Effects of Kojic Acid in Aβ-Induced Mouse Model of Alzheimer’s Disease - Amjad Khan; Tae Ju Park; Muhammad Ikram; Sareer Ahmad; Riaz Ahmad; Min Gi Jo; Myeong Ok Kim (Molecular Neurobiology, 2021)

Agricultural water management challenges in the Hunza River Basin: Is a solar water pump an alternative option?* - Madhav Prasad Dhakal; Amjad Ali; Muhammad Zafar Khan; Nisha Wagle; Ghulam Muhammad Shah; Muhammad Mudassar Maqsood; Ajaz Ali (Irrigation and Drainage, 2021)
In the glaciated mountains of the Upper Indus Basin of Pakistan, glacier‐ and snowmelt‐ based irrigation systems have been established over several centuries to secure water for cultivation. However, these systems are now facing several challenges, being sensitive to climate change and thus exposed to the resulting extreme events such as glacial lake outburst floods (GLOFs) and flash floods, also difficult terrain and access paths, male outmigration, limited technical capacity and a weak policy and governance system. Hence, exploring the potential options for overcoming the challenges and irrigating arable barren land could lead to economic prosperity and environmental gains. A literature review, stakeholder consultation and semi‐structured questionnaire survey in two villages of the Hunza River basin was conducted to synthesize information in different domains. Information on the irrigation system and its sources, water distribution/allocation system, challenges and adaptation strategies were collected, and based on community preferences, an alternative irrigation technological package was established to overcome the challenges and irrigate barren land. A customized solar water lifting pump with an efficient micro‐irrigation package was piloted which proved to be climate resilient. The system is simple to adopt, uses clean energy for operation and is economically feasible, with a benefit–cost ratio of 4.96 and a payback period of around 11 years.

Assessment of heavy metal content of commonly consumed herbal medicines in Sindh, Pakistan - Amjad Hussain Soomro; Wahid Bux Jatoi; Amjad Ali Maitlo; Almas Fatima Memon; Muhammad Siddique Bhayo (Environmental Science and Pollution Research, 2021)

CO2 separation by supported liquid membranes synthesized with natural deep eutectic solvents - Usman Saeed; Asim Laeeq Khan; Mazhar Amjad Gilani; Muhammad Aslam; Asad Ullah Khan (Environmental Science and Pollution Research, 2021)

The impacts of land use/land cover changes on the supply-demand budget of urban ecosystem services - Syed Atif Bokhari; Zafeer Saqib; Amjad Ali; Arif Mahmud; Nadia Akhtar; Ambrina Kanwal; Muhammad Zaman ul Haq (Arabian Journal of Geosciences, 2021)

Chemical composition of gemstones and characterization of their host pegmatites and country rocks from Chumar Bakhoor, Gilgit-Baltistan, Pakistan: implications for the source of gem-forming fluids - Amjad Hussain; Muhammad Tahir Shah; Mohammad Arif; Muhammad Hassan Agheem; Muhammad Saleem Mughal; Shakir Ullah; Syed Asim Hussain; Izhar Sadiq (Arabian Journal of Geosciences, 2021)

Biostratigraphic investigation and depositional model of the Late Thanetian Ranikot and the Ypresian Laki formations in the subsurface of the Southern Indus Basin, Pakistan - Hussain Asghar; Muhammad Saleem Mughal; Muhammad Sabir Khan; Saeed Abbas; Muhammad Hanif; Gulfam Hussain; Muhammad Ali; Kazim Ali; Amjad Hussain (Arabian Journal of Geosciences, 2021)

Factors influencing the combined efficacy of microbial insecticides and inert dusts for the control of Trogoderma granarium - Rameesha Amjad Ali; Mansoor ul Hasan; Muhammad Sagheer; Shahbaz Talib Sahi; Amer Rasul (International Journal of Tropical Insect Science, 2021)

Clove (Syzygium aromaticum) and its phytochemicals in ruminant feed: an updated review - Muhammad Saeed; Muhammad S. Khan; Mahmoud Alagawany; Mayada R. Farag; Othman Alqaisi; Amjad I. Aqib; Muhammad Qumar; Faisal Siddique; Mohamed Fawzy Ramadan (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)

Comparative toxicity of transgenic cotton CEM-33, Bt-906 varieties, and Annona squamosa L., seed extract against biotic potential of Spodoptera litura (Fab.) - Qurban Ali Arain; Muhammad Farhanullah Khan; Habibullah Rana; Amjad Sultan; Zubair Ahmed; Hakim Ali Sahito; Muhammad Asif Farooq; Muhammad Faheem Akbar; Tasneem Kousar (International Journal of Tropical Insect Science, 2021)

Effect of green human resource management practices on organizational sustainability: the mediating role of environmental and employee performance - Fiza Amjad; Waseem Abbas; Muhammad Zia-UR-Rehman; Sajjad Ahmad Baig; Muhammad Hashim; Ayesha Khan; Hakeem-ur- Rehman (Environmental Science and Pollution Research, 2021)

Distribution and health risk assessment of trace elements in ground/surface water of Kot Addu, Punjab, Pakistan: a multivariate analysis - Zafar Abbas; Muhammad Imran; Natasha Natasha; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Iftikhar Ahmad; Sajjad Ahmad (Environmental Monitoring and Assessment, 2021)

Enhancing socioeconomic resilience and climate adaptation through value chain development of mountain products in Hindu Kush Himalayas - Saranjam M. Baig; Aftab A. Khan; Amjad Ali; Muhammad Zafar Khan; Sultan Ahmed; Ghulam M. Shah; Ghulam Ali (Environment, Development and Sustainability, 2021)

Molecular docking of alpha-enolase to elucidate the promising candidates against Streptococcus pneumoniae infection - Muhammad Hassan; Atif Amin Baig; Syed Awais Attique; Shafqat Abbas; Fizza Khan; Sara Zahid; Qurat Ul Ain; Muhammad Usman; Nordin Bin Simbak; Mohammad Amjad Kamal; Hanani Ahmad Yusof (DARU Journal of Pharmaceutical Sciences, 2021)

Assessment of Zinc, Lead, Chromium, and Cobalt in Commonly Consumed Herbal Medicines in Sindh, Pakistan - Amjad Ali Maitlo; Wahid Bux Jatoi; Almas Fatima Memon; Amjad Hussain Soomro; Muhammad Siddique Bhayo (Biological Trace Element Research, 2021)

Genetic architecture of wild soybean (Glycine soja Sieb. and Zucc.) populations originating from different East Asian regions - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Hon-Ming Lam; Faheem Shehzad Baloch; Muhammad Amjad Ali; Kirill S. Golokhvast; Seung Hwan Yang; Gyuhwa Chung (Genetic Resources and Crop Evolution, 2021)

Molecular epidemiology of Coxiella Brunetii in small ruminants in Punjab, Pakistan: a novel reporting analytical cross sectional study - Muhammad Zahid Iqbal; Aneela Zameer Durrani; Jawaria Ali Khan; Nisar Ahmad; Muhammad Usman; Abdul Jabbar; Amjad Khan; Saba Usman; Ahsan Anjum; Muhammad Husnain (Tropical Animal Health and Production, 2021)

Relative Effectiveness of Phosphorus and Potassium Along with Compost and Organic Acids on Maize Crop Grown in Calcareous Soil: a Multivariate Analysis - Saira Tabbasum; Muhammad Akhtar; Nadeem Sarwar; Muhammad Imran Tipu; Wasiq Ikram; Arooba Ashraf; Amjad Ejaz; Behzad Murtaza; Muhammad Rizwan Khan (Journal of Soil Science and Plant Nutrition, 2021)

Delineating Novel Therapeutic Drug and Vaccine Targets for Staphylococcus cornubiensis NW1T Through Computational Analysis - Mohibullah Shah; Samavia Jaan; Batool Fatima; Muhammad Sameem Javed; Adnan Amjad; Asifullah Khan; Sahib Gul Afridi; Umar Nishan; Anwar Iqbal; Haq Nawaz (International Journal of Peptide Research and Therapeutics, 2021)

Physicomechanical, stability, and pharmacokinetic evaluation of aceclofenac dimethyl urea cocrystals - Hafsa Afzal; Nasir Abbas; Amjad Hussain; Sumera Latif; Kanwal Fatima; Muhammad Sohail Arshad; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2021)

First report of leaf spot of bottle gourd (Lagenaria siceraria) caused by Fusarium equiseti in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Sabin Aslam; Muhammad Amjad Ali; Nasir Ahmad Khan; Yingyan Zhai; Mark L. Gleason (Journal of Plant Pathology, 2021)

Influence of indigenous plant materials on reproductive performance of Callosobruchus chinensis (L.) (Coleoptera: Bruchidae) on chickpea - Bilawal Nizamani; Mushtaque Ahmed Agha; Qurban Ali; Amjad Hussain; Hakim Manghwar; Muhammad Kamran; Aafaque Ahmed Keerio; Zeeshan Ahmed Solangi; Muhammad Akbar Lashari; Din Muhammad Soomro (International Journal of Tropical Insect Science, 2020)

The role of financial development, tourism, and energy utilization in environmental deficit: evidence from 20 highest emitting economies - Muhammad Usman; Rakhshanda Kousar; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2020)

First report of root rot caused by Ceratobasidium sp. AG-Fa on Capsicum annuum in Pakistan - Aliya Tariq; Farah Naz; Muhammad Shahid; Amjad Shahzad Gondle; Abdul Sattar; Muhammad Nabeel; Zobia Jabeen; Imran Hassan (Journal of Plant Pathology, 2020)

An empirical nexus between economic growth, energy utilization, trade policy, and ecological footprint: a continent-wise comparison in upper-middle-income countries - Muhammad Usman; Rakhshanda Kousar; Muhammad Rizwan Yaseen; Muhammad Sohail Amjad Makhdum (Environmental Science and Pollution Research, 2020)

Dietary intake assessment of pyrethroid residues from okra and eggplant grown in peri-urban areas of Punjab, Pakistan - Adnan Amjad; Muhammad Atif Randhawa; Muhammad Sameem Javed; Zafarullah Muhammad; Mussawar Ashraf; Zulfiqar Ahmad; Shamas Murtaza (Environmental Science and Pollution Research, 2020)

Partial Substitution of Fishmeal with Plant Protein Source the Soybean Meal in the Diets of Arabian Yellowfin Seabream Acanthopagrus arabicus Juveniles - Naveed Ahmad; Jamal Pirzada A. Siddiqui; Ghulam Nabi; Khan Mir Khan; Amjad Ali; Yasmeen Zamir; Mohammad Abdul Momin Siddique; Shabir Ali Amir; Farah Naz Khokhar; Muhammad Amin (Thalassas: An International Journal of Marine Sciences, 2020)

Effective sequestration of Cr (VI) from wastewater using nanocomposite of ZnO with cotton stalks biochar: modeling, kinetics, and reusability - Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Hussnain Siddique; Zafar Iqbal; Muhammad Amjad; Muhammad Rizwan; Shafaqat Ali (Environmental Science and Pollution Research, 2020)

Bioaccumulation of potentially toxic elements in spinach grown on contaminated soils amended with organic fertilizers and their subsequent human health risk - Zawar Hussain; Mehboob Alam; Muhammad Amjad Khan; Muhammad Asif; Muhammad Azhar Shah; Shehnaz Khan; Sardar Khan; Javed Nawab (Arabian Journal of Geosciences, 2020)

Hydrogeochemical investigation of arsenic in drinking water of schools and age dependent risk assessment in Vehari District, Punjab Pakistan: a multivariate analysis - Behzad Murtaza; Humaira Nazeer; Natasha; Muhammad Amjad; Muhammad Imran; Muhammad Shahid; Noor S. Shah; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Murtaza (Environmental Science and Pollution Research, 2020)

Compositional and health risk assessment of drinking water from health facilities of District Vehari, Pakistan - Behzad Murtaza; Natasha; Muhammad Amjad; Muhammad Shahid; Muhammad Imran; Noor Samad Shah; Ghulam Abbas; Muhammad Asif Naeem; Muhammad Amjad (Environmental Geochemistry and Health, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

Cadmium Partitioning, Physiological and Oxidative Stress Responses in Marigold (Calendula calypso) Grown on Contaminated Soil: Implications for Phytoremediation - Amjad Farooq; Muhammad Nadeem; Ghulam Abbas; Arslan Shabbir; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Farhan Saeed; Ahsan Akram; Adnan Younis; Gulzar Akhtar (Bulletin of Environmental Contamination and Toxicology, 2020)

Assessment of antibiotics use for children upper respiratory tract infections: a retrospective, cross-sectional study from Pakistan - Zia Ul Mustafa; Muhammad Salman; Alina Zeeshan Rao; Noman Asif; Sanan Amjad Butt; Naureen Shehzadi; Khalid Hussain (Infectious Diseases, 2020)

Occurrence of heavy metals and pesticide residues in tomato crop: a threat to public health - Muhammad Ishaq; Nighat Sultana; Muhammad Ikram; Amjad Iqbal; Farooq Shah; Muhammad Hamayun; Anwar Hussain (Arabian Journal of Geosciences, 2020)

The efficacy of sustainability reporting towards cost of debt and equity reduction - Muhammad Kashif Shad; Fong-Woon Lai; Amjad Shamim; Michael McShane (Environmental Science and Pollution Research, 2020)

Yucasin and cinnamic acid inhibit IAA and flavonoids biosynthesis minimizing interaction between maize and endophyte Aspergillus nomius - Asif Mehmood; Anwar Hussain; Muhammad Irshad; Muhammad Hamayun; Amjad Iqbal; Abdul Tawab; Naeem Khan (Symbiosis, 2020)

Effect of biochar and phosphate solubilizing bacteria on growth and phosphorus uptake by maize in an Aridisol - Muhammad Arif Ali; Muhammad Mustansar Ajaz; Muhammad Rizwan; Muhammad Farooq Qayyum; Muhammad Arshad; Sajjad Hussain; Niaz Ahmad; Muhammad Amjad Qureshi (Arabian Journal of Geosciences, 2020)

Testing the effect of different insecticides on Myzus persicae (Homoptera: Aphididae) in field mustard (Brassicae campestris L.) Czern for possible consideration in an IPM strategy - Muhammad Shahbaz Khan; Muhammad Faheem Akbar; Amjad Sultan; Muhammad Shoaib Saleem; Chand Gul (International Journal of Tropical Insect Science, 2020)

Molecular characterization of genetic diversity and similarity centers of safflower accessions with ISSR markers - Fawad Ali; Muhammad Azhar Nadeem; Ephrem Habyarimana; Abdurrahim Yılmaz; Muhammad Amjad Nawaz; Iftikhar Hussain Khalil; Sezai Ercişli; Gyuhwa Chung; Hassan Javed Chaudhary; Faheem Shehzad Baloch (Brazilian Journal of Botany, 2020)

Impact assessment of land use and climate changes on the variation of runoff in Margalla Hills watersheds, Pakistan - Muhammad Shahid; Khalil Ur Rahman; Khaled S. Balkhair; Amjad Nabi (Arabian Journal of Geosciences, 2020)

Linking traditional anti-ulcer use of rhizomes of Bergenia ciliata (Haw.) to its anti-Helicobacter pylori constituents - Ejaz Ali; Najma Arshad; Nadeem Irfan Bukhari; Muhammad Nawaz Tahir; Shamail Zafar; Amjad Hussain; Sajida Parveen; Shaista Qamar; Naureen Shehzadi; Khalid Hussain (Natural Product Research, 2020)

First report of post-harvest rot of Citrus reticulata cv. ‘Kinnow’ caused by Rhizopus arrhizus in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Aman Ullah Malik; Mark Lawrence Gleason; Binyamin Rana; Muhammad Amjad Ali (Journal of Plant Pathology, 2020)

In Vivo Evaluation of a Novel Chitosan-Polycaprolactone Based Mucoadhesive Gastro-Retentive Sustained Release Drug Delivery System for Milnacipran HCl - Talib Hussain; Muhammad Ijaz; Rahat Shamim; Khalid Hussain; Nasir Abbas; Amjad Hussain; Julia Anita Griessinger; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2020)

Study of land cover/land use changes using RS and GIS: a case study of Multan district, Pakistan - Sajjad Hussain; Muhammad Mubeen; Waseem Akram; Ashfaq Ahmad; Muhammad Habib-ur-Rahman; Abdul Ghaffar; Asad Amin; Muhammad Awais; Hafiz Umar Farid; Amjad Farooq; Wajid Nasim (Environmental Monitoring and Assessment, 2020)

Assessment of arsenic exposure by drinking well water and associated carcinogenic risk in peri-urban areas of Vehari, Pakistan - Ali Haidar Shah; Muhammad Shahid; Sana Khalid; Natasha; Zunaira Shabbir; Hafiz Faiq Bakhat; Behzad Murtaza; Amjad Farooq; Muhammad Akram; Ghulam Mustafa Shah; Wajid Nasim; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2020)

Genome-wide analysis of spatiotemporal gene expression patterns during floral organ development in Brassica rapa - Soo In Lee; Muthusamy Muthusamy; Muhammad Amjad Nawaz; Joon Ki Hong; Myung-Ho Lim; Jin A. Kim; Mi-Jeong Jeong (Molecular Genetics and Genomics, 2019)

Functional Annotation and Analysis of Dual Oxidase 1 (DUOX1): a Potential Anti-pyocyanin Immune Component - Muhammad Ibrahim Rashid; Amjad Ali; Saadia Andleeb (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Mixed matrix membranes incorporated with sonication-assisted ZIF-8 nanofillers for hazardous wastewater treatment - Mohsin Ali; Muhammad Aslam; Amin Khan; Mazhar Amjad Gilani; Asim Laeeq Khan (Environmental Science and Pollution Research, 2019)

Improved transdermal delivery of cetirizine hydrochloride using polymeric microneedles - Muhammad Sohail Arshad; Sana Hassan; Amjad Hussain; Nasir Abbas; Israfil Kucuk; Kazem Nazari; Radeyah Ali; Suleman Ramzan; Ali Alqahtani; Eleftherios G. Andriotis; Dimitris G. Fatouros; Ming-Wei Chang; et al. (DARU Journal of Pharmaceutical Sciences, 2019)

Hesperetin Confers Neuroprotection by Regulating Nrf2/TLR4/NF-κB Signaling in an Aβ Mouse Model - Muhammad Ikram; Tahir Muhammad; Shafiq Ur Rehman; Amjad Khan; Min Gi Jo; Tahir Ali; Myeong Ok Kim (Molecular Neurobiology, 2019)

Novel antimicrobial and antioxidative activity by endophytic Penicillium roqueforti and Trichoderma reesei isolated from Solanum surattense - Muhammad Ikram; Niaz Ali; Gul Jan; Muhammad Hamayun; Farzana Gul Jan; Amjad Iqbal (Acta Physiologiae Plantarum, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Foliar uptake of arsenic nanoparticles by spinach: an assessment of physiological and human health risk implications - Natasha; Muhammad Shahid; Camille Dumat; Sana Khalid; Faiz Rabbani; Abu Bakr Umer Farooq; Muhammad Amjad; Ghulam Abbas; Nabeel Khan Niazi (Environmental Science and Pollution Research, 2019)

Melatonin Rescue Oxidative Stress-Mediated Neuroinflammation/ Neurodegeneration and Memory Impairment in Scopolamine-Induced Amnesia Mice Model - Tahir Muhammad; Tahir Ali; Muhammad Ikram; Amjad Khan; Sayed Ibrar Alam; Myeong Ok Kim (Journal of Neuroimmune Pharmacology, 2019)

Management of hyperuricemia through dietary polyphenols as a natural medicament: A comprehensive review - Arshad Mehmood; Lei Zhao; Chengtao Wang; Muhammad Nadeem; Ali Raza; Nawazish Ali; Amjad Abbas Shah (Critical Reviews in Food Science and Nutrition, 2019)

Biogeochemical behavior of nickel under different abiotic stresses: toxicity and detoxification mechanisms in plants - Nuzhat Ameen; Muhammad Amjad; Behzad Murtaza; Ghulam Abbas; Muhammad Shahid; Muhammad Imran; Muhammad Asif Naeem; Nabeel K. Niazi (Environmental Science and Pollution Research, 2019)

Geochemical attributes of late Neoproterozoic Salt Range Formation, Pakistan: constraints on provenance, paleoclimate, depositional and tectonic settings - Muhammad Ahmed Farooqui; Muhammad Umar; Muhammad Amjad Sabir; Rashid Pervez; Tarib Jalees (Geosciences Journal, 2019)

Genome-wide identification and expression analyses of WRKY transcription factor family members from chickpea (Cicer arietinum L.) reveal their role in abiotic stress-responses - Muhammad Waqas; Muhammad Tehseen Azhar; Iqrar Ahmad Rana; Farrukh Azeem; Muhammad Amjad Ali; Muhammad Amjad Nawaz; Gyuhwa Chung; Rana Muhammad Atif (Genes & Genomics, 2019)

Characterization of Cellulose Synthase A (CESA) Gene Family in Eudicots - Muhammad Amjad Nawaz; Xiao Lin; Ting-Fung Chan; Muhammad Imtiaz; Hafiz Mamoon Rehman; Muhammad Amjad Ali; Faheem Shehzad Baloch; Rana Muhammad Atif; Seung Hwan Yang; Gyuhwa Chung (Biochemical Genetics, 2019)

Integrated use of biochar and compost to improve soil microbial activity, nutrient availability, and plant growth in arid soil - Muhammad Akmal; Zubaira Maqbool; Khalid Saifullah Khan; Qaiser Hussain; Shahzada Sohail Ijaz; Muhammad Iqbal; Irfan Aziz; Amjad Hussain; Muhammad Subtain Abbas; Hafeez Ullah Rafa (Arabian Journal of Geosciences, 2019)

Assessment of Circulating Biochemical Markers in Mice Receiving Cinnamon and Glycyrrhizin Under Carbon Tetrachloride Induced Hepatic Injury - Mahmood Rasool; Arif Malik; Sadia Saleem; Shakeel Ahmed Ansari; Javed Iqbal; Muhammad Asif; Mohammed Amjad Kamal; Mohammed Hussain Al-Qahtani; Sajjad Karim (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Endocrine disrupting pesticides in soil and their health risk through ingestion of vegetables grown in Pakistan - Neelum Ali; Sardar Khan; Muhammad Amjad Khan; Muhammad Waqas; Huaiying Yao (Environmental Science and Pollution Research, 2019)

In vitro production of IAA by endophytic fungus Aspergillus awamori and its growth promoting activities in Zea mays - Asif Mehmood; Anwar Hussain; Muhammad Irshad; Muhammad Hamayun; Amjad Iqbal; Naeem Khan (Symbiosis, 2019)

A multivariate analysis of physiological and antioxidant responses and health hazards of wheat under cadmium and lead stress - Behzad Murtaza; Faryal Naeem; Muhammad Shahid; Ghulam Abbas; Noor S. Shah; Muhammad Amjad; Hafiz Faiq Bakhat; Muhammad Imran; Nabeel Khan Niazi; Ghulam Murtaza (Environmental Science and Pollution Research, 2019)

Tattooing trend: major cause of HCV transmission among youngsters - Braira Wahid; Komal Saleem; Nouman Rasool; Shazia Rafique; Amjad Ali; Muhammad Waqar; Muhammad Idrees (Infectious Diseases, 2018)

Role of Zinc–Lysine on Growth and Chromium Uptake in Rice Plants under Cr Stress - Afzal Hussain; Shafaqat Ali; Muhammad Rizwan; Muhammad Zia ur Rehman; Amjad Hameed; Farhan Hafeez; Saud A. Alamri; Mohammed Nasser Alyemeni; Leonard Wijaya (Journal of Plant Growth Regulation, 2018)

Erratum to: Molecular Elucidation of Two Novel Seed Specific Flavonoid Glycosyltransferases in Soybean - Hafiz Mamoon Rehman; Muhammad Amjad Nawaz; Zahid Hussain Shah; Gyuhwa Chung; Seung Hwan Yang (Journal of Plant Biology, 2018)

Cadmium (Cd) concentration in wheat (Triticum aestivum) grown in Cd-spiked soil varies with the doses and biochar feedstock - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Irfan Sohail; Amjad Hussain; Muhammad Farooq Qayyum; Hinnan Khalid; Muhammad Zeeshan; Naveeda Majid (Arabian Journal of Geosciences, 2018)

Molecular epidemiology of bovine anaplasmosis in Khyber Pakhtunkhwa, Pakistan - Shahid Hussain Farooqi; Muhammad Ijaz; Muhammad Imran Rashid; H. Nabi; S. Islam; Amjad Islam Aqib; Kashif Hussain; Amjad Khan; Syeda Nayab Batool Rizvi; Shakeel Mahmood; Khalid Mehmood; Hui Zhang (Tropical Animal Health and Production, 2018)

Plant growth promoting endophytic fungi Asprgillus fumigatus TS1 and Fusarium proliferatum BRL1 produce gibberellins and regulates plant endogenous hormones - Lubna Bilal; Sajjad Asaf; Muhammad Hamayun; Humaira Gul; Amjad Iqbal; Ihsan Ullah; In-Jung Lee; Anwar Hussain (Symbiosis, 2018)

Pb fractionation and redistribution as affected by applied inorganic amendments under different soil moisture regimes and incubation time in saline–sodic Pb-polluted paddy soil - Muhammad Mazhar Iqbal; Ghulam Murtaza; Tayyaba Naz; Amjad Hussain; Mark Button; Gijs Du Laing (Paddy and Water Environment, 2018)

Molecular Elucidation of Two Novel Seed Specific Flavonoid Glycosyltransferases in Soybean - Hafiz Mamoon Rehman; Muhammad Amjad Nawaz; Zahid Hussain Shah; Gyuhwa Chung; Seung Hwan Yang (Journal of Plant Biology, 2018)

Simultaneously Improving Mechanical, Formulation, and In Vivo Performance of Naproxen by Co-Crystallization - Nasir Abbas; Sumera Latif; Hafsa Afzal; Muhammad Sohail Arshad; Amjad Hussain; Saleha Sadeeqa; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2018)

Gibberellins application timing modulates growth, physiology, and quality characteristics of two onion (Allium cepa L.) cultivars - Salman Mushtaq; Muhammad Amjad; Khurram Ziaf; Irfan Afzal (Environmental Science and Pollution Research, 2018)

Concentrations, dietary exposure, and human health risk assessment of heavy metals in market vegetables of Peshawar, Pakistan - Mehboob Alam; Maaz Khan; Anwarzeb Khan; Shah Zeb; Muhammad Amjad Khan; Noor ul Amin; Muhammad Sajid; Abdul Mateen Khattak (Environmental Monitoring and Assessment, 2018)

Genome-Wide Analysis of Potassium Transport-Related Genes in Chickpea (Cicer arietinum L.) and Their Role in Abiotic Stress Responses - Farrukh Azeem; Bilal Ahmad; Rana Muhammad Atif; Muhammad Amjad Ali; Habibullah Nadeem; Sabir Hussain; Hamid Manzoor; Muhammad Azeem; Muhammad Afzal (Plant Molecular Biology Reporter, 2018)

New natural product -an efficient antimicrobial applications of new newly synthesized pyrimidine derivatives by the electrochemical oxidation of hydroxyl phenol in the presence of 2-mercapto-6-(trifluoromethyl) pyrimidine-4-ol as nucleophile - Zia Ul Haq Khan; Amjad Khan; Pingyu Wan; Arif Ullah Khan; Kamran Tahir; Nawshad Muhammad; Faheem Ullah Khan; Hidayat Ullah Shah; Zia Ullah Khan (Natural Product Research, 2018)

Determination of the role of salicylic acid and Benzothiadiazole on physico-chemical alterations caused by Cucumber mosaic virus in tomato - Rana M. Sabir Tariq; Khalid P. Akhtar; Amjad Hameed; Najeeb Ullah; Muhammad Y. Saleem; Imran ul Haq (European Journal of Plant Pathology, 2018)

Suppression of PGE2 production via disruption of MAPK phosphorylation by unsymmetrical dicarbonyl curcumin derivatives - Mohd Fadhlizil Fasihi Mohd Aluwi; Kamal Rullah; Md. Areeful Haque; Bohari M. Yamin; Waqas Ahmad; Muhammad Wahab Amjad; Sze Wei Leong; Nurul Amira Fahmizar; Juriyati Jalil; Faridah Abas; Nor Hadiani Ismail; Ibrahim Jantan; et al. (Medicinal Chemistry Research, 2017)

Molecular docking and glucosidase inhibition studies of novel N-arylthiazole-2-amines and Ethyl 2-[aryl(thiazol-2-yl)amino]acetates - Ayesha Babar; Muhammad Yar; Hamadeh Tarazi; Vera Duarte; Mohammed B. Alshammari; Mazhar Amjad Gilani; Haffsah Iqbal; Munawwar Ali Munawwar; Maria J. Alves; Ather Farooq Khan (Medicinal Chemistry Research, 2017)

Potentially Toxic Metals and Biological Contamination in Drinking Water Sources in Chromite Mining-Impacted Areas of Pakistan: A Comparative Study - Javed Nawab; Sardar Khan; Muhammad Amjad Khan; Hassan Sher; Ubaid Ur Rehamn; Sharafat Ali; Syed Mehboob Shah (Exposure and Health, 2017)

Assessment of heavy metals concentration in phosphate rock deposits, Hazara basin, Lesser Himalaya Pakistan - Faridullah Faridullah; Muhammad Umar; Arif Alam; Muhammad Amjad Sabir; Danyal Khan (Geosciences Journal, 2017)

MPD3: a useful medicinal plants database for drug designing - Arooj Mumtaz; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Farooq Anwar; Faisal Gulzar; Muhammad Amjad Ali; Nazamid Saari; Muhammad Tariq Pervez (Natural Product Research, 2017)

RETRACTED ARTICLE: Beta-cyanoalanine synthase pathway as a homeostatic mechanism for cyanide detoxification as well as growth and development in higher plants - Hafiz Mamoon Rehman; Zahid Hussain Shah; Muhammad Amjad Nawaz; Muhammad Qadir Ahmad; Seung Hwan Yang; Kang Hee Kho; Gyuhwa Chung (Planta, 2017)

Genome-wide characterization and expression pattern of auxin response factor (ARF) gene family in soybean and common bean - Bao Le; Muhammad Amjad Nawaz; Hafiz Mamoon Rehman; Thu Le; Seung Hwan Yang; Kirill S. Golokhvast; Eunho Son; Gyuhwa Chung (Genes & Genomics, 2016)

Comparative enzyme inhibition study of 1-deazapurines - Iftikhar Ali; Ajmal Khan; Amjad Hussain; Umar Farooq; Muhammad Ismail; Viqar Hyder; Viqar U. Ahmad; Viktor O. Iaroshenko; Hidayat Hussain; Peter Langer (Medicinal Chemistry Research, 2016)

Computing soil creep velocity using dendrochronology - Mohammad Amjad Sabir; Muhammad Umar; Muhammad Farooq; Faridullah Faridullah (Bulletin of Engineering Geology and the Environment, 2016)

Rotavirus infections in Detroit, USA, a region of low vaccine prevalence - Nahed Abdel-Haq; Muhammad Amjad; Eric McGrath; Hossein Salimnia; Marilynn Fairfax; Basim I. Asmar (VirusDisease, 2016)

A New Broad-Spectrum Peptide Antibiotic Produced by Bacillus brevis Strain MH9 Isolated from Margalla Hills of Islamabad, Pakistan - Syed Aun Muhammad; Amjad Ali; Anam Naz; Afreenish Hassan; Naeem Riaz; Syed Saeed-ul-Hassan; Saadia Andleeb; Debmalya Barh (International Journal of Peptide Research and Therapeutics, 2016)

Differential accumulation of potassium results in varied salt-tolerance response in tomato (Solanum lycopersicum L.) cultivars - Muhammad Amjad; Javaid Akhtar; Behzad Murtaza; Ghulam Abbas; Husnain Jawad (Horticulture, Environment, and Biotechnology, 2016)

Health risk assessment from contaminated foodstuffs: a field study in chromite mining-affected areas northern Pakistan - Javed Nawab; Gang Li; Sardar Khan; Hassan Sher; Muhammad Aamir; Isha Shamshad; Anwarzeb Khan; Muhammad Amjad Khan (Environmental Science and Pollution Research, 2016)

Relationship between rhizosphere acidification and phytoremediation in two acacia species - Ghulam Abbas; Muhammad Saqib; Javaid Akhtar; Ghulam Murtaza; Muhammad Shahid; Amjad Hussain (Journal of Soils and Sediments, 2016)

Amberinone, a new guaianolide from Amberboa ramosa - Muhammad Ibrahim; Iqbal Hussain; Nusrat Hussain; Arruje Hameed; Tahir Farooq; Amjad Hussain; Muhammad Sajid Hamid Akash; Shabbir Hussain (Natural Product Research, 2016)

The uptake and bioaccumulation of heavy metals by food plants, their effects on plants nutrients, and associated health risk: a review - Anwarzeb Khan; Sardar Khan; Muhammad Amjad Khan; Zahir Qamar; Muhammad Waqas (Environmental Science and Pollution Research, 2015)

Evaluation of weather research and forecasting model for the assessment of wind resource over Gharo, Pakistan - Muhammad Amjad; Qudsia Zafar; Firdos Khan; Muhammad Munir Sheikh (International Journal of Climatology, 2015)
Weather research and forecasting (WRF) model is the state‐of‐the‐art mesoscale model that could be used as a guideline to effectively assess the wind resource of Gharo wind station lying in the coastal belt of Pakistan. The anemometer heights of 10 and 30 m for the year 2005 have been used to study the wind profile of the region for summer (June, July, August, September) and winter (December, January, February, March). The study uses an innovative approach for model comparisons, i.e. an eta‐half level is added in the model on 60 m height and is interpolated to 30 m height by using well known power law. This is done by studying the diurnal variation of wind shear for the whole year of 2005 in order to reduce maximum possible interpolation error. For both seasons, the error measures of mean bias error (MBE), mean absolute error (MAE) and root mean square error (RMSE) of 30 m interpolated data were found lower than 10 m height data with increased correlation ( r ). A bias correction methodology (best easy systematic estimator) was further applied over the model output showing a significant improvement toward MBE, MAE and RMSE reduction, i.e. up to 99%, 73% and 68% on 10 m height and 99%, 51% and 46% on 30 m height. Errors were reduced more for summer than winter. The selected bias correction methodology was thus found to be highly applicable for both model heights. The wind energy assessment of Gharo wind station from the corrected model simulation showed summer having more potential for wind energy than winter with an estimated energy of up to 1000 MWh.

Stratigraphic and sedimentological attributes in Hazara Basin Lesser Himalaya, North Pakistan: their role in deciphering minerals potential - Muhammad Umar; Muhammad Amjad Sabir; Muhammad Farooq; Malik Muhammad Saud Sajid Khan; Faridullah Faridullah; Umair Khan Jadoon; Abdul Salam Khan (Arabian Journal of Geosciences, 2015)

Studies on the role of neutralizing antibodies against envelope genes in resolving HCV pseudo-particles infection - Shazia Rafique; Muhammad Idrees; Amjad Ali; Muhammad Iqbal (Molecular Biology Reports, 2014)

Generation of infectious HCV pseudo typed particles and its utilization for studying the role of CD81 & SRBI receptors in HCV infection - Shazia Rafique; Muhammad Idrees; Amjad Ali; Kashif Iqbal Sahibzada; Muhammad Iqbal (Molecular Biology Reports, 2014)

Microsatellite analysis of Rosa damascena from Pakistan and Iran - Amjad Farooq; Mahnaz Kiani; Muhammad Aslam Khan; Atif Riaz; Asif Ali Khan; Natalie Anderson; David H. Byrne (Horticulture, Environment, and Biotechnology, 2013)

Studies in a consanguineous family reveal a novel locus for stuttering on chromosome 16q - Muhammad Hashim Raza; Rana Amjad; Sheikh Riazuddin; Dennis Drayna (Human Genetics, 2012)

Study of heritable variation and genetics of earliness in mungbean (Vigna radiata L. Wilczek) - Aziz ur Rehman; Muhammad Amjad Ali; Muhammad Saleem; W. Tadesse (Euphytica, 2010)

Correlative evidence for peroxidase involvement in disease resistance against Alternaria leaf blight of tomato - Amjad Hameed; Khalid Pervaiz Akhtar; Muhammad Yussouf Saleem; Muhammad Asghar (Acta Physiologiae Plantarum, 2010)

Effect of post-irradiation ageing on onion seeds - Muhammad Amjad; Muhammad Akbar Anjum (Acta Physiologiae Plantarum, 2007)